Non-destructive quality estimation and internal pigmentation discrimination of ‘Sanguinelli’ blood oranges using hyperspectral imaging - Salvador Castillo-Girones; María E. García-Pastor; María Serrano; Daniel Valero; Sergio Cubero; Salvador Castillo (Food Control, 2026)

First record of angiosperm fossil leaf from the Coris Formation (middle Miocene) of the Central Valley, Costa Rica - Marco A. Rubalcava-Knoth; Mario A. Blanco; Rafael Acuña-Castillo; Guillermo E. Alvarado; Luis A. Gamboa; Sergio R.S. Cevallos-Ferriz (Journal of South American Earth Sciences, 2026)

Endocrine disrupting chemicals and their effects on mosquito vectors of infectious diseases: A narrative review - Valeria Vargas; Guadalupe E. Ángeles-López; Jorge Cime-Castillo; Mariana Segovia-Mendoza (Environmental Pollution, 2026)

Beyond Rare: Documenting Albino‐Like Phenotypes as a Recurring Trait in the Juan Fernandez Fur Seal - Constanza Toro‐Valdivieso; Renato Borras‐Chavez; Víctor Castillo‐González; Luciano Hiriart‐Bertrand; Michael E. Goebel; Barbara Blacklaws (Marine Mammal Science, 2026)

Imaging sweetness: Rapid permeation of sucrose into rice callus cells as a component of cryoprotectant solutions - Albert Ochoa-Castillo; Gayle M. Volk; Nancy E. Levinger (Cryobiology, 2026)

La1: an evolutionarily conserved player in the Arabidopsis telomerase complex - Chinmay Phadke; Saundarya K. Mishra; Jiarui Song; Rebekah Holtsclaw; Claudia Castillo Gonzalez; Ishan Kundel; Edward M. Marcotte; Ophelia Papoulas; Dorothy E. Shippen (Plant Cell Reports, 2026)
Key message Quantitative mass spectrometry of Arabidopsis telomerase uncovered AtLa1, a homolog of ciliate and yeast proteins that promotes telomerase maturation. AtLa1 is essential for telomerase function in vivo, and in vitro it engages the same region of AtTR bound by AtNAP57, homologous to a telomerase accessory from mammals. Abstract Striking divergence is evident in the biogenesis pathways and protein complements of telomerase from mammals and single-cell organisms. However, little is known about plant telomerase. Along with catalytic subunit TERT and templating RNA TR, we previously showed Arabidopsis thaliana telomerase is also associated with AtNAP57, a dyskerin homolog essential for mammalian telomerase biogenesis. Here we employ quantitative mass spectrometry (qMS) to uncover additional Arabidopsis telomerase constituents. We report AtLa1 as a new telomerase-associated protein. RNA-IP assays confirmed AtLa1 association with AtTR, while transient RNAi-mediated knockdown of AtLa1 strongly diminished telomerase activity, supporting a functional role for AtLa1 in telomere maintenance in vivo. In vitro binding studies revealed AtLa1 contacts AtTR via the UUU-3′OH and a plant-specific P1a-P1b-P4 three-way junction (TWJ). Notably, the TWJ is also required for AtNAP57 association with AtTR. However, this protein was not detected in our qMS experiment using overexpressed AtTERT and AtTR, perhaps because the purification scheme enriched for RNP assembly intermediates. La-related proteins serve as RNA chaperones and are associated with a wide variety of telomerase complexes. Therefore, we postulate that AtNAP57 and AtLa1 compete for AtTR or bind sequentially during telomerase biogenesis. Further exploration of Arabidopsis telomerase may offer novel insights into telomerase evolution and mechanisms of biogenesis.

Deep Phylogenomic Structure and Microendemism in Baja California Ammotrechidae (Arachnida: Solifugae) Support a Model of Distributed Diversification - Matthew R. Graham; Carlos E. Santibáñez‐López; R. Ryan Jones; Joshua A. Idjadi; Athenea M. Acosta; Fadia Sara Ceccarelli; Jaír R. Castillo; Diana Laura Batista‐Perales; Jack O. Brookhart; Paula E. Cushing (Journal of Biogeography, 2026)
Aim To assess phylogeographic structure, phylogenetic diversity and historical diversification processes in ammotrechid camel spiders from the Baja California Peninsula. Location Baja California Sur, Mexico. Time Period Miocene to Pleistocene. Major Taxa Studied Ammotrechid camel spiders (Solifugae: Ammotrechidae). Methods We conducted the first phylogeographic analysis of Baja California Sur ammotrechid camel spiders using mitochondrial COI sequences and genome‐wide RADseq data. Phylogenomic analyses, divergence dating, species accumulation curves and tests of admixture (F 3 statistics) were used to evaluate lineage structure, timing of diversification and patterns of connectivity. Results We uncovered deep phylogenomic structure and extensive cryptic diversity, identifying at least 16 putative lineages, many restricted to single localities. Divergence dating indicates Miocene origins with subsequent Plio–Pleistocene diversification. Although several lineages exhibit north–south structure, divergence times and spatial patterns do not support diversification driven by discrete transpeninsular seaway vicariance at major southern breaks (e.g., La Paz/Loreto). Instead, patterns support a model of distributed diversification shaped by tectonic segmentation, habitat heterogeneity, and climatic oscillation. Limited admixture among a subset of closely related lineages, suggested by incongruent tree topologies and F 3 statistics, indicates episodic secondary contact rather than long‐term connectivity. Species accumulation curves did not approach an asymptote, suggesting that much of the region's solifuge diversity remains undocumented. Main Conclusions Ammotrechid camel spiders preserve fine‐scale genomic signatures of landscape history in Baja California Sur and reveal previously undocumented levels of endemism and diversification. These results highlight Solifugae as promising but underused systems for geogenomic studies of desert biogeography.

Ready for European turtle dove adaptive harvest management? Lessons learned from pilot trials in Extremadura (south-western Spain) - Carlos Sánchez-García; José Luis Guzmán; Raquel Castillo-Contreras; Davide Carniato; Gregorio Rocha; Miguel Gómez; Juan Rubiales; Ángel Hurtado; Carlos Lázaro; E. Jorge Tizado; Luis F. Villanueva (Journal for Nature Conservation, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

In search of an effective and safe anesthetic in decapod crustaceans: Insights from Procambarus clarkii - I. Ruiz-Jarabo; L. Herrera-Castillo; D. Madera; N. Saiz; E. Isorna; M.J. Delgado; N. de Pedro (Aquaculture, 2026)

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Agroecological factors influencing the activity, diversity and distribution of nematophagous fungi in some Mediterranean olive grove soils - Rosana Salazar-García; Antonio Archidona-Yuste; Víctor Valenzuela-Polo; Inmaculada Garrido-Jurado; Pablo Castillo; Juan E. Palomares-Rius (Plant and Soil, 2026)
Aims The olive tree is a major crop in Mediterranean countries, but its cultivation faces growing challenges due to climate change. Nematophagous fungi are considered key components of soil ecosystems and can potentially control plant-parasitic nematode populations. This study aims to explore the diversity of these fungi in Mediterranean olive groves, assess their potential for controlling plant-parasitic nematodes, and identify the factors that influence this activity. Study design Forty-two olive groves across four countries (Greece, Morocco, Portugal and Spain) and two management practices (organic and non-organic) were sampled. Methodology The diversity and activity of nematophagous fungi were assessed using two approaches. First, nematodes community DNA extracted from 500 cm 3 of soil was analysed via qPCR to quantify six target fungi actively attacking the nematodes population. Second, an egg-bait in vitro bioassay was used to detect the broader presence of nematophagous fungi at each site. Results Important differences in nematophagous fungi diversity and activity were found among countries, but not by olive grove management. Greece had the most diverse and active nematophagous fungi. Fungal ovicidal activity was significantly related to climatic conditions, as aridity increased, the infection rate decreased. According to the qPCR results, Purpureocillium lilacinum was the most prevalent and was detected in all countries. Drechslerella dactyloides, Orbilia oligospora and Hirsutella rhossiliensis had low prevalence. Catenaria sp. and Gamsylella gephyropaga were not detected. Conclusion Organic management does not necessarily increase the presence and diversity of nematophagous fungi in olive Mediterranean groves which appear primarily influenced by climatic and edaphic conditions.

Assessment of the taxonomic distinctness in natural protected areas on the Mesoamerican reef in Mexico - Karen Monserrat Chel-Ramírez; Julieta Maldonado-Sánchez; Diana E. Morales de Anda; Aarón Israel Muñiz-Castillo; Melanie McField; Jesús Ernesto Arias-González (Regional Studies in Marine Science, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Alternative male mating tactics and direct benefits via spermatophore transfer in the neotropical cricket Macroanaxipha macilenta (Saussure, 1897) - Anahi Elias-Quevedo; Mario E. Favila; Raúl Cueva del Castillo (Journal of Insect Behavior, 2026)
Male crickets transfer sperm via a spermatophore, which also contains compounds that enhance ovulation, egg hatching, and the female's longevity. These compounds also may induce mechanisms to guarantee males’ paternity. In Macroanaxipha macilenta (Saussure, 1897) , there are two male morphs, the Wide-Forewing, and the Narrow-Forewing. During mating, Wide-Forewing males transfer one spermatophore to the female, whereas Narrow-Forewing males transfer two. We analyzed the effects of spermatophores on the fecundity and lifespan of females mated with Wide-Forewing and Narrow-Forewing males. While both types of spermatophores contain sperm, reproductive success varied between the two groups. We found that 41.37% of the females mated with Wide-Forewing and 30.46% of the females mated with Narrow-Forewing males had offspring. The study shows that while spermatophore consumption does not affect fecundity. Moreover, females mated with Narrow-Forewing males had a longer lifespan than females mated with Wide-Forewing males. Our results suggest that Wide-Forewing and Narrow-Forewing males might represent alternative mating tactics with different payoffs.

The IPBES invasion-management framework supports informed decision-making for managing biological invasions - Chika Egawa; K. V. Sankaran; Andy W. Sheppard; Evangelina Schwindt; Llewellyn C. Foxcroft; Sonia Vanderhoeven; Lora Peacock; Maria L. Castillo; Rafael D. Zenni; Jana Müllerová; Ana Isabel González Martínez; John K. Bukombe; et al. (Biological Invasions, 2026)
The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) Thematic Assessment Report on Invasive Alien Species and Their Control presents a “conceptual diagram of management-invasion continuum”, introducing a versatile framework to support decision-making on the management of biological invasions. Drawing on an extensive synthesis of current knowledge, this IPBES invasion-management framework has been developed to broaden the scope of existing invasion curves—which primarily overlay generic management objectives onto a sigmoid curve depicting the expansion of the affected area over time—and to illustrate the applicability of the concept of effective management at different stages of the biological invasion process. To introduce the IPBES invasion-management framework to a wider audience, this paper explains the features of the framework and defines the invasion-stage-based management approaches and the potential outcomes envisaged therein. Reflecting the currently limited management options for biological invasions in marine and other connected-water systems, unlike in terrestrial and closed-water systems, the IPBES invasion-management framework clearly distinguishes between these two groups of systems. For each, it presents management approaches including three key factors that decision-makers should consider concurrently: management objectives, targets, and actions. This framework supports informed decision-making in the management of biological invasions in all ecosystems.

Community-centered approaches to aquaculture in small-scale fisheries - Liliana Sierra Castillo; Christine Knott; Anastasia C. E. Quintana; Ana K. Spalding; Erendira Aceves-Bueno; Jessica Blythe; Antonella Rivera; Bonnie Basnett (Ambio, 2026)
Aquaculture is the fastest-growing seafood production system globally, offering economic and social opportunities for small-scale fishing communities. Yet, it is often introduced through top-down, technocratic approaches that ignore the social-ecological realities of these communities. Drawing on four case studies from Mexico and Honduras, this study uses a multistage, participatory mixed-methods approach to examine the integration of aquaculture into existing fisheries. We focus on governance, social organization, economic assets, and cultural traditions, key yet understudied dimensions of implementation. Findings reveal that projects overlooking these interactions risk deepening inequities, displacing traditional livelihoods, and weakening community cohesion. Success depends on early economic support, recognition of local traditions and social structures, and the creation of context-specific governance systems. Centering community needs and experiences can help design equitable, place-based aquaculture initiatives that strengthen, rather than disrupt, small-scale fishing livelihoods.

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.

Vitamin B12 improves skeletal muscle mitochondrial biology in aged mice - Abigail R. Williamson; Angad Yadav; Wenxia Ma; Susan Schmitt; Shelby Rorrer; Lauren E. Odom; Luisa F. Castillo; Chloe T. Purello; Olga V. Malysheva; James Mobley; Martha Field; Anna E. Thalacker-Mercer (GeroScience, 2026)
Age-related skeletal muscle deterioration is a commonly reported disability among older adults, attributed to several factors including mitochondrial dysfunction, a major hallmark of aging. Therapies to attenuate or reverse mitochondrial decline are limited. Despite identified positive relationships between vitamin B12 (B12) and mitochondrial biology, the impact of B12 supplementation on skeletal muscle mitochondria, in advanced age, has not been examined. Thus, the impact of B12 supplementation on skeletal muscle mitochondrial biology was examined in aged female mice, given 12 weeks of B12 supplementation (SUPP) or vehicle control. In the mouse model, mitochondrial DNA and content were measured with PCR and citrate synthase activity, respectively; mitochondrial morphology was examined using transmission electron microscopy; mitochondrial function was examined using extracellular metabolic flux analysis; and proteins and pathway enrichment was identified with proteomics. The results demonstrated that SUPP in aged mice increased muscle mitochondrial content and improved morphology. Further, differentially expressed proteins were enriched in TCA cycle, OXPHOS, and oxidative stress pathways. This is the first study, to our knowledge, examining the impact of B12 supplementation on skeletal muscle mitochondrial biology in aged female mice. Results suggest that B12 supplementation improves mitochondrial biology in aged female mice.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Fungal endophytes and their secondary metabolites for crop protection - Jorge Rojas López-Menchero; Fotios A. Lyssaios; Nicolás Reyes-Castillo; Maria Fe Andres; Azucena González-Coloma; Carmen E. Díaz (Journal of Pest Science, 2026)
Fungal endophytes have emerged as a promising strategy for sustainable crop management, due to their remarkable ability to synthesize a wide array of secondary metabolites with beneficial effects on plants. These microorganisms establish asymptomatic relationships within plant tissues and can produce bioactive compounds with biocidal properties. Despite promising advances, the mechanisms of symbiosis remain unclear and there is a lack of in-depth analysis on the chemical characterization of their metabolites. This review compiles and discusses the current discoveries on 180 metabolites summarized according to their biological activities (insecticidal, antifungal, phytotoxic, nematicidal and antibacterial), highlighting their potential applications as biocontrol agents for integrated crop protection strategies. As a future perspective, the use of next-generation sequencing (NGS) technologies such as metagenomics in endophytic fungi research is emphasized for its promise in elucidating complex plant–microbe interactions and guiding bioprospecting efforts to identify fungal taxa capable of producing agriculturally relevant bioactive compounds. This review aims to summarize recent advances in the field, highlighting the potential uses of endophytic compounds in plant health, disease suppression, and resistance enhancement, while also identifying current limitations and outlining future research directions to further expand this promising area.

Tectonomagmatic evolution of the volcano vent cluster of the Tzirate Range in Mexico - Mario E. Boijseauneau-López; Giovanni Sosa-Ceballos; Daniel Tapia-Flores; Antonio Pola; José Luis Macías; Miguel E. Castillo-Rodríguez; Xavier Bolós (Bulletin of Volcanology, 2026)
The Tzirate Range (TR; 1.5–0.93 Ma) is a volcanic vent cluster within the Michoacán-Guanajuato Volcanic Field (2.5 Ma–present), composed of effusive andesitic to rhyolitic rocks that reflect complex, multi-stage magmatic evolution. By integrating geochemical, mineralogical, isotopic, and morpho-structural data, this study reveals that magma differentiation in the TR was driven by fractional crystallization, magma mixing, and assimilation of crustal material within shallow reservoirs, under tectonic control exerted by the reactivation of basement faults. The rocks exhibit a calc-alkaline affinity with elevated δ 1 ⁸O values (+ 7.23 to + 9.43) and isotopic signatures (⁸⁷Sr/⁸⁶Sr = 0.70370–0.70431; εNd = 1.82–4.27 ± 0.33, 1σ), consistent with crustal contamination. Disequilibrium textures (e.g., resorption rims, patchy zoning) and mineral compositions (An 39–60 , En 43–79 ) reflect open-system processes and dynamic magma evolution. Hydrothermal assimilation experiments support incorporation of granitic material at ~ 880–900 °C and ~ 180 MPa. In addition, morphometric analysis of drainage networks using knickpoint detection and normalized steepness index ( K sn ) enables the identification of reactivated basement faults that control the magmatic plumbing system. Therefore, it demonstrates the utility of K sn -based morphometric analysis as a robust and complementary tool for identifying hidden tectonic systems in volcanic terrains with limited surface exposure. These findings suggest that the TR vent cluster represents a transitional stage between monogenetic and polygenetic volcanism, highlighting the influence of tectonic controls on vent distribution and long-term volcanic evolution. This interdisciplinary approach provides new insights into the mechanisms controlling the development and dynamics of volcanic clusters by characterizing their plumbing systems and structural frameworks.

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Neurobiological effects assessment in wild rodents exposed to mercury in Sierra Gorda Biosphere Reserve, Querétaro, Mexico - S. Vargas-Ruiz; C.G. Castillo; E. Rubio-Hernández; A. Gavilán-García; F. Díaz-Barriga; G. Espinosa-Reyes (Chemosphere, 2026)

Dynamics of coastal picoeukaryote communities in response to oil spill disturbances - B. Glasner; I. Morel-Letelier; E. Osses; C. Galvez-Aracena; P. Ávila-Guerrero; C. Henríquez-Castillo; E. Urrejola-Pulido; C.B. Pareja; A.A. Durán; N. Trefault; R. De la Iglesia (Marine Environmental Research, 2026)

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Unprecedented heat stress and coral bleaching in 2023: a regional assessment from the Bay Islands of Honduras - Rebecca H. Green; Ángela Randazzo-Eisemann; Andrea Rivera-Sosa; Aaron Israel Muñiz-Castillo; Antonella Rivera; Pamela Ortega; Mayra Núñez-Vallecillo; Claudia Guerrero; Paolo Guardiola; Gisselle Brady; Helen E. Fox (Coral Reefs, 2026)

Physiological and transcriptomic responses to fasting-refeeding in Arapaima gigas: Insights into compensatory growth for aquaculture production - T.H. Delgadin; L.E. Santos-Rojas; D. Medina-Herrera; N.M. Herrera-Castillo; A.M. Alonso; A. Saavedra-Flores; E.A. López-Landavery; J.I. Fernandino; E. Zelada-Mázmela (Aquaculture, 2026)

Sex-specific nutritional requirements of mating in insects with contrasting mating systems - C. Ruth Archer; Matthew R. Carey; Charles E. Grant; Clarissa House; Amy Molotoks; Enrique del Castillo; Zeya Wagner; John Hunt (Animal Behaviour, 2026)

Microbial consortia in mine water bioremediation: principles, design and practical applications - A. Matu; A. Valverde; E. Cason; A. Gomez-Arias; M. Maleke; J. Castillo (Water Research, 2026)

Historical activity (1522–2025) of the Masaya volcano in Nicaragua and characterization of Pelé's hair and tears from the 2016 eruption - Guillermo E. Alvarado-Induni; Hugo Delgado-Granados; Martha Navarro-Collado; Arnoldo Castillo-Ferrufino; María Martínez-Cruz; Ariadna Calderón; Carlos Linares-López; Reinaldo Pereira-Reyes; Alexis Debut; Virginia Tenorio; Theofilos Toulkeridis (Journal of South American Earth Sciences, 2026)

Spatio-temporal analysis of record-breaking temperature increments across Spain - Ana C. Cebrián; Jesús Asín; Jorge Castillo-Mateo; Alan E. Gelfand (Stochastic Environmental Research and Risk Assessment, 2026)
The study of record-breaking values is of significant interest in environmental sciences. Studying records implies analyzing both their occurrence and their magnitude. Further, the study of this phenomenon within a spatio-temporal framework is vital for evaluating seasonal behaviors, identifying spatial patterns, and quantifying the effect of climate change on it. With interest in record-breaking temperatures, we specify models for these observations rather than models for the entire daily temperature stream. Models specifically designed for record-breaking events must consider two random components: the occurrence and the magnitude of each record. With primary interest in the magnitudes, we model the magnitude data given the occurrence data, with the goal of making inference about their evolution within a spatio-temporal framework. We employ a set of 40 geo-referenced time series of daily temperatures across peninsular Spain. From these, we extract the series of occurrences and values of record-breaking events during the summer months, June, July, and August, spanning from 1960 to 2021. The results reveal that the behavior of the increments is neither spatially nor temporally homogeneous, and that there is significant dependence on the previous day: the occurrence of a record increases the posterior mean of the next day’s increment by between 0.3 and 0.6 °C. It is also found that the posterior mean of the average increment on a record-breaking day during the decade 2012–2021 is approximately 1 °C inland, increasing to around 2°C in some coastal areas. After 30 years, mean increments stabilize near 1°C with a mild downward trend.

Revisiting Small‐Scale Aquaculture ( SSA ) - Liliana Sierra Castillo; Halley E. Froehlich; Jono R. Wilson; Jessica A. Gephart; Erendira Aceves‐Bueno; Steven D. Gaines (Reviews in Aquaculture, 2026)
Aquatic foods are a vital source of nutrition, yet growing demand and stagnant wild‐capture fisheries have positioned aquaculture as essential to meeting global food needs. Despite this, aquaculture's diverse forms remain poorly understood, particularly small‐scale aquaculture (SSA). Unlike small‐scale fisheries (SSF), which are widely recognized in policy and research, SSA lacks consistent definitions and is often conflated with SSF or defined narrowly by physical metrics like farm size. This limits its visibility in policy and development efforts, overlooking critical social, economic, and governance dimensions such as ownership, labor, and market orientation. Through a systematic review of 83 studies across 24 countries, we analyze SSA across ecosystems (freshwater, brackish, marine) and species groups (finfish, invertebrates, seaweed) to identify trends in production characteristics, yield reporting, and social dimensions. We find freshwater SSA dominates the literature, while marine SSA, especially mollusk farming, is significantly underrepresented. SSA exhibits wide variation in yields, farm sizes, ownership, and management structures, indicating that existing classification frameworks are insufficient. We propose a context‐sensitive, social‐ecological classification system that integrates production metrics with governance and socioeconomic characteristics. To guide application, we offer two policy frameworks, one for regions with existing SSA definitions, recommending participatory revision and expanded data collection; and one for regions without definitions, advocating for a stepwise approach to characterization. Our findings underscore the need for more inclusive, adaptable classifications to improve SSA's visibility in global food policy and unlock its full contributions to sustainable development, equity, and local livelihoods.

Acute toxicity of frog-skin-homologous synthetic alkaloids and frog-skin extracts: miniaturized test to evaluate toxicity with Daphnia magna - Michael Méndez-Rivera; Didier Ramírez-Morales; Abel Mora-Machado; Heike Pröhl; Ariel Rodríguez; Vásquez-Cháves Victor; Mantzana-Oikonomaki Vasiliki; Takuya Okada; Naoki Toyooka; Roberto Ibáñez; Carlos E. Rodríguez-Rodríguez; Giselle Tamayo-Castillo (Toxicon, 2025)

Floristic diversity as a reference for the conservation of the sky islands of the Chihuahuan Archipelago - Jesús E. Sáenz-Ceja; José Á. Villarreal-Quintanilla; David Castillo-Quiroz (Journal for Nature Conservation, 2025)

Philippine functional foods: A new frontier in noncommunicable diseases prevention - Myra O. Villareal; Lotis E. Mopera; Gladys C. Completo; Ruel C. Nacario; Marissa V. Romero; Katherine Ann T. Castillo-Israel; Rona Camille M. Lizardo-Agustin; Marianne Joy G. Laya; Roi Miguel M. Obdosantos; Christel Leo O. Romano; Jocelyn E. Serrano; Samuel C. Bobiles; et al. (Food and Humanity, 2025)

Visualizing sucrose permeability into live plant cells using coherent Raman microscopy - Albert Ochoa-Castillo; Fionna M.D. Samuels; Nancy E. Levinger (Cryobiology, 2025)

A New Neotropical Species of Gnathostoma (Nematoda: Gnathostomatidae) from the Northern Four-Eyed Opossum Philander vossi (Marsupialia) - M. Á. Mosqueda-Cabrera; E. Sánchez-Miranda; L. D. Castillo-Loeza; G. Torres-Carrera; L. García-Prieto (Acta Parasitologica, 2025)
Purpose This work provides a detailed morphological description of a previously identified but unnamed lineage inside Gnathostoma spp. from Mexico. Methods Specimens of the four-eyed opossum Philader vossi were collected in Tlacotalpan, Veracruz, Mexico. Specimens were examined morphologically using both light microscopy and scanning electron microscopy. Additionally, we generate DNA sequences for the following loci: mitochondrial cox 1 and nuclear 5.8S rRNA and ITS-2 and 28S rDNA. Results The new species, Gnathostoma mexicanum n. sp., differs from G. turgidum Stossich, 1902, the common gnathostomid species infecting Didelphis spp. from the Americas, in its smaller body size, fewer teeth on the cuticular spines at anterior half of body, as well as site of infection (pyloric region vs. stomach layers). Host specificity further distinguishes the two species. Additionally, molecular data show that the new species clearly diverges from its congeners. Conclusions This work represents the fourth Gnathostoma species described for Mexican mammals and the eight recorded in the Americas.

Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Martin Calianno; Daniel A. Castillo; Santiago I. Hurtado; Saúl Deluchi; Brenda Garcia; Laura Villar; E. Sebastian Villagra; Marcos H. Easdale (Small Ruminant Research, 2025)

Nutrition Assessment in Cyclic Vomiting Syndrome: Exploring the Prevalence of Avoidant/Restrictive Food Intake Disorder, Disordered Eating, and Metabolic Dysregulation - L. Forsthoefel; G. Vanhouwe; O. Khan; K. Heitman; K. Goheen; E. Holley; P. Madril; J. Kennel; R. Jimenez-Castillo; S. Arumugam; M. Vyas; P. Goday; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge E. Chira-Fernandez; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Journal of Environmental Chemical Engineering, 2025)

Aquaculture isn’t always the answer: rethinking blue transitions through justice and community experience - Liliana Sierra Castillo; Caroline E. Ferguson Irlanda; Erendira Aceves-Bueno; Halley E. Froehlich; Cristina Mancilla; Antonella Rivera; Steven D. Gaines (Global Environmental Change, 2025)

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Conservation Arks: Genomic Erosion and Inbreeding in an Abundant Island Population of Koalas - Katie Gates; Jonathan Sandoval‐Castillo; Julian E. Beaman; Karen Burke da Silva; Frédérik Saltré; Katherine Belov; Carolyn J. Hogg; Corey J. A. Bradshaw; Luciano B. Beheregaray (Molecular Ecology, 2025)
The persistence of many threatened species depends on isolated habitat patches such as conservation parks, fenced reserves, and islands. While these ‘conservation arks’ provide refuge from many contemporary threats, they can also pose risks of genetic diversity loss and inbreeding depression, further exacerbating extinction risk. A pertinent example is the Kangaroo Island koala population in South Australia that originated from a few translocated founding individuals in the 1920s but now sustains a large population with a low prevalence of infectious disease. We investigated the extent and consequences of founder effects on genomic diversity, inbreeding, and adaptive potential in Kangaroo Island koalas by comparing them with mainland Australian populations using high‐coverage whole genomes. Our findings support sharp, recent declines in effective population sizes ( N e ) in both mainland and Kangaroo Island populations. However, Kangaroo Island koalas had much lower individual and population‐level diversity. Together with longer and more numerous runs of homozygosity and an increased proportion of homozygous genetic load, these results support the hypothesis that a severe bottleneck has contributed to inbreeding and maladaptation in Kangaroo Island koalas. While Kangaroo Island has the potential to conserve a viable population of koalas, we recommend genetic rescue to restore diversity and mitigate inbreeding depression in this isolated population. Our results emphasise the need for longitudinal genomic monitoring and genetic management to maintain long‐term viability and resilience in potential conservation arks. Understanding the demographic history of such populations will help inform future conservation aimed at preventing genetic erosion and preserving biodiversity.

Mathematical modelling of kinetic and breakthrough curves for Cd(II) adsorption onto Sargassum biomass using the Diffusion – Permeation Model - Lázaro Adrián González-Fernández; Samuel Aguirre-Contreras; Nahum Andrés Medellín-Castillo; Manuel Sánchez-Polo; Amado Enrique Navarro-Frómeta; Roberto Leyva-Ramos; Javier E. Vilasó-Cadre; Raúl Ocampo-Pérez (Journal of Water Process Engineering, 2025)

From past to present: Shifting landscape drivers of dung beetle functional and phylogenetic diversity in a tropical reserve - José D. Rivera-Duarte; Renato P. Salomão; Eduardo Ulises Castillo-Pérez; Juan José Von Thaden; Alejandro Espinosa de los Monteros; Mario E. Favila (Journal of Environmental Management, 2025)

Impacts of heat stress under oceanic climate on fertility and reproductive physiology of dairy cows subjected to hormonal synchronization - E. N. Martínez; C. Castillo; L. Avendaño-Reyes; J. Hernández; J. L. Benedito; A. Rico; P. Garcia; R. Muiño (International Journal of Biometeorology, 2025)
Regions with oceanic climates are experiencing unprecedented climatic changes. This study assesses the presence of heat stress in these regions and its impact on reproductive in Holstein cows using the Temperature-Humidity Index (THI), a measure of thermal stress. Data was collected from 159 Holstein cows across experiments. Cows underwent a modified double-ovsynch synchronization protocol, while 96 cows were inseminated based on observed estrous. Cows were examined for body temperature, follicle and uterus examination, and serum progesterone concentrations to evaluate the impact of heat stress. The results of cows pregnancy rate in double-ovsynch synchronized cows were 48.5% and 43.3% in summer and winter seasons, respectively. While the pregnancy rate in non-synchronized cows were 29.5% and 32.7% in summer and winter season, respectively. Elevated THI levels (THI ≥ 72) have adversely effects on reproductive physiology, reduced estrous expression, decreased uterine blood flow, and altered progesterone concentrations. Mild heat stress during summer months in oceanic climate negatively impacted reproductive efficiency in dairy cows, for adaptive management strategies. The double-ovsynch protocol effectively stabilized fertility across seasons, demonstrating its value in improving reproductive outcomes under varying thermal conditions.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Effective in vitro bulbification and alkaloid dereplication by GC-MS of Chilean Zephyranthes splendens, an endemic species of the Andes mountains - Ricardo E. Hernández; Jean Paulo de Andrade; Natalia Opazo; Ignacia Castillo; Strahil Berkov; Ariel D. Arencibia (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Chronic arsenic exposure of ovarian surface and fallopian tube cultures induces giant and/or multinucleated cells with phagocytosis-like properties and an inflammatory phenotype - Cristina M. Andrade-Feraud; Arlet M. Acanda de la Rocha; Noah E. Berlow; Santiago Duque; Alexander Velazco; Diego Castillo; Baylee Holcomb; Ebony R. Coats; Yasmin R. Ghurani; Catherine M. Lucey; Brandon Pearson; Tomás R. Guilarte; et al. (Toxicology and Applied Pharmacology, 2025)

Canine eosinophilic pulmonary granulomatosis: Clinical-pathological diagnosis and physiopathology theories - L.X. Bravo-Coello; E. Carrillo-Castillo; A. Cervantes-Arias; M. Juárez-Ramírez; G. Valero-Elizondo (Journal of Comparative Pathology, 2025)

Herbicides in Argentine Pampas Shallow Lakes and Frequency of Testicular Lesions in the Pejerrey Fish (Odontesthes bonariensis) - Nicolás Torres Martínez; Diego Cristos; Ariadna A. Castillo; Gustavo E. Berasain; Pedro Carriquiriborde; Leandro A. Miranda (Bulletin of Environmental Contamination and Toxicology, 2025)

Effect of long-term retrogradation on the crystallinity, vibrational and rheological properties of potato, corn, and rice starches - Gonzalo Velazquez; Cristian Felipe Ramirez-Gutierrez; Guadalupe Mendez-Montealvo; Rodrigo Velazquez-Castillo; Luis Fernando Morelos-Medina; Eduardo Morales-Sánchez; Marcela Gaytán-Martínez; Mario E. Rodríguez-García; Brenda Contreras-Jiménez (Food Chemistry, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Assessment of Tunisian clays for their potential application as excipient in pharmaceutical preparations: 2-amino-5-chlorobenzophenone adsorption - Safa Gamoudi; Jihene Manai; Wilfried G. Kanhounnon; Didilia Ileana Mendoza-Castillo; Adrián Bonilla-Petriciolet; Yann Foucaud; George E. Christidis; Ezzeddine Srasra; Michael Badawi (Applied Clay Science, 2025)

Using a vibrating microtome to prepare Mentha × piperita shoot tip sections for live-tissue microscopy experiments - Heidi D. Kreckel; Albert Ochoa-Castillo; Stephanie Villanueva; Gayle M. Volk; Nancy E. Levinger (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Occurrence of pharmaceuticals in muscle tissue of red drum (Sciaenops ocellatus) across subtropical estuaries: Comparison to blood plasma and implications for human exposure - W. Ryan James; Nicholas A. Castillo; Andy Distrubell; Shakira Trabelsi; Rolando O. Santos; Daniel Cerveny; Ryan J. Rezek; Ross E. Boucek; Aaron J. Adams; Jerker Fick; Tomas Brodin; Jennifer S. Rehage (Science of The Total Environment, 2025)

Hematology and serum biochemistry reference intervals for the common opossum Didelphis marsupialis - Claudia P. Ceballos; Estefanía Aristizábal-Parra; Viviana E. Castillo-Vanegas (Veterinary Research Communications, 2025)
The common opossum, Didelphis marsupialis , is a neotropical and synanthropic marsupial common and widespread in Latin America. The strong human-opossum conflict that results in high numbers of individuals with health problems demands information on physiological parameters to be used in veterinary medicine practice. The aim of this study was to estimate the reference intervals (RI) of hematology and serum biochemistry for this species which are lacking and evaluate its variability. Out of the 61 apparently healthy wild opossums evaluated, we found significant variability in the RI´s associated sex, life stage, habitat, and the reproductive stage of females. Males had higher values of RBC and hemoglobin than females, but females had higher values of MCH than males. Juveniles had higher values of MCV and MCH, but adults had higher values RBC, WBC and neutrophils. In addition, rural opossums had higher values of hemoglobin, MCHC, MCH and platelets, but urban opossums had higher values of WBC, particularly neutrophils and lymphocytes. Opossums are exposed to many different stressors in urban settings, and further research is needed to understand these physiological responses to urbanization. Finally, lactating females had higher values of monocytes and basophils compared to non-lactating females, potentially providing passive immunity through the milk to the immature neonates in the marsupium.

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Effect of pH, temperature and adsorbent mass on Cr (VI) adsorption in residues from a coal washing plant - Aime J. Garcia-Lugo; Jorge C. Ríos-Hurtado; Gloria I. Dávila-Pulido; Adrián A. González-Ibarra; Fatima P. Lara-Castillo; Sergio E. Flores-Villaseñor (Environmental Geochemistry and Health, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Unveiling the diversity of macrobenthic crustaceans on sandy beaches of the eastern Mexican coast: new records and an updated checklist - María R. Muciño-Reyes; Edlin Guerra-Castro; Raúl E. Castillo-Cupul; Carlos E. Paz-Ríos; Nuno Simões (Frontiers in Marine Science, 2025)
Despite the ecological importance of sandy beaches, the diversity and distribution of macrocrustacean communities in the eastern Mexican coast (Mexican coast of the Gulf of Mexico and Caribbean Sea) remain understudied. As the first large-scale sampling effort along the eastern Mexican coast, this study aimed to estimate macrocrustacean diversity and evaluate sampling methodologies, while providing historical context for macrocrustacean research in the region. Two sampling designs using sediment cores (4 versus 6 cores per transect) were implemented across 15 sandy beaches. A total of 3,352 organisms were collected, representing 22 species from 17 genera, spanning 14 families, 7 suborders, 5 orders, and 2 superorders. Amphipoda and Isopoda exhibited the highest species richness and abundance. The study yielded seven new geographical records ( Haustorius jayneae , Rhepoxynius epistomus , Americorchestia salomani , Heterodina mosaica , Cassidinidea ovalis , Exosphaeroma diminutum , and Sphaeroma walkeri ). Results demonstrated that the 6-core sampling design provided better diversity representation. An updated checklist comprising 77 species/taxa for the eastern Mexican coast was compiled, integrating historical and new data. This comprehensive assessment enhances our understanding of these vulnerable ecosystems and emphasizes the need for broader temporal and spatial scale studies to inform effective conservation strategies.

Unraveling the role of chitosan in enhancing the photodegradation of ciprofloxacin by using chitosan-titanates composites: Experimental and in-silico approach - V. Castro-Velázquez; P.C. Hernández-Del Castillo; E. Díaz-Cervantes; V. Rodríguez-González (Journal of Environmental Management, 2025)

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Modular comparison of untargeted metabolomics processing steps - Markus Aigensberger; Christoph Bueschl; Ezequias Castillo-Lopez; Sara Ricci; Raul Rivera-Chacon; Qendrim Zebeli; Franz Berthiller; Heidi E. Schwartz-Zimmermann (Analytica Chimica Acta, 2025)

Bee pollination affects coffee quality, yield, and trade-offs within them - Natalia Aristizábal; Silvia E. Mora-Mena; Alejandra Martínez-Salinas; Adina Chain-Guadarrama; Danny Castillo; Juan B. Murillo; Jimmy Porras; Taylor H. Ricketts (Agriculture, Ecosystems & Environment, 2025)

Small-scale geographic differences in multiple-driver environmental variability can modulate contrasting phenotypic plasticity despite high levels of gene flow - Nicole Castillo; Juan Diego Gaitán-Espitia; Julian F. Quintero-Galvis; Gonzalo S. Saldías; Sebastián I. Martel; Marco A. Lardies; Andrés Mesas; Iván E. Pérez-Santos; Stefan Gelcich; Cristian A. Vargas (Science of The Total Environment, 2024)

Interfacial behaviour of human bile and its substitution for in vitro lipolysis studies - Dorota Dulko; Ilona E. Kłosowska-Chomiczewska; Teresa del Castillo-Santaella; Miguel A. Cabrerizo-Vílchez; Justyna Łuczak; Robert Staroń; Łukasz Krupa; Julia Maldonado-Valderrama; Adam Macierzanka (Food Research International, 2024)

Techno-functional properties and structural characteristics of cricket protein concentrates affected by pre-treatments and ultrafiltration/diafiltration processes - Alejandro Davalos-Vazquez; Luis Mojica; Oscar Abel Sánchez-Velázquez; Gustavo Castillo-Herrera; Judith E. Urías-Silvas; Alain Doyen; Lorena Moreno-Vilet (Food Chemistry, 2024)

Sucrose interactions with plant cells and tissue: Insights into cryoprotective mechanisms - Albert Ochoa-Castillo; Katherine Nelson; Fionna M.D. Samuels; Nancy E. Levinger (Cryobiology, 2024)

Cadmium availability in rhizosphere and non-rhizosphere soils in cacao farms in Santander, Colombia - C. A. Adarme-Duran; J. Ágreda; P. F. B. Brandão; E. Castillo (Environmental Monitoring and Assessment, 2024)
Current research has highlighted the need to understand the factors influencing cadmium (Cd) availability in cacao-growing soils to elucidate its presence in cacao beans (the raw material for chocolate). Although literature about this topic is increasing, few report the importance of rhizosphere soils on Cd dynamics. This study aimed to understand the changes in available Cd and its association with soil properties (pH, pseudo-total Cd, available Cd (Cd-DTPA), Ca, Mg, K, Na, soil organic carbon, P, Zn, urease activity, exchangeable acidity, and cation exchange capacity) considering rhizosphere and non-rhizosphere soils. Both soil types (51 samples of each, 102 in total) were collected from two Colombian cacao farms. The medians of pseudo-total Cd (1.86 mg kg −1 ) and Cd-DTPA (0.76 mg kg −1 ) were, respectively, about threefold and fourfold higher in rhizosphere compared to non-rhizosphere soils. Principal component analysis showed a clear distinction between rhizosphere and non-rhizosphere soils based on differences in soil properties, which explained the observed changes in available Cd when comparing both soil types. Soil organic carbon and Zn were important drivers of available Cd in rhizosphere soils. Spatial distribution analysis revealed a tendency of available Cd to cluster in rhizosphere soils, and indicated hotspots within each farm. These findings highlight the importance of rhizosphere soils for Cd diagnosis and monitoring, and for improving knowledge about Cd dynamics in the soil- Theobroma cacao L. system.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Theoretical and experimental study of adsorption and catalytic reactivity of asphaltene fractions A1 and A2 over cubic NiO–PdO/CeO2 nanoparticles - Oscar E. Medina; Ivan Moncayo Riascos; Samira Heidari; Sócrates A. Acevedo; Jimmy Castillo; Farid B. Cortés; Camilo A. Franco (Fuel, 2024)

Extraction of bio-hydroxyapatite from devilfish (Loricariidae) for the fluoride and cadmium adsorption from water and its feasible photocatalytic properties - Hilda G. Cisneros-Ontiveros; Luis F. Zubieta-Otero; Nahum A. Medellín-Castillo; Alfredo I. Flores-Rojas; Mario E. Rodriguez-Garcia (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

New study of the adsorption mechanism of different dye molecules by high porous sludge activated carbon produced from a dairy-treatment effluent plant - Angélica F.M. Streit; Hercules A. Pereira; Jaime Moreno-Pérez; Didilia I. Mendoza-Castillo; Hilda E. Reynel-Ávila; Kátia da Boit Martinello; Luis F.O. Silva; Naushad Ahmad; Sonaimuthu Mohandoss; Adrián Bonilla-Petriciolet; Guilherme L. Dotto (Journal of Environmental Chemical Engineering, 2024)

Does the diversity of vegetation and diatoms correlate with soil and water factors in a tropical cloud forest’s complex land use/land cover scenario? - Gabriela Vázquez; José G. García-Franco; Gonzalo Castillo-Campos; M. Luisa Martínez; Klaus Mehltreter; Adolfo Campos; Mario E. Favila (Environmental Monitoring and Assessment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P26-01 Hexagonal boron nitride (hBN) and hBN-reinforced thermoplastic polyurethane composite: an in vitro hazard characterization using human skin and lung cells - M. Carlin; J. Kaur; D.Z. Ciobanu; Z. Song; M. Olsson; T. Totu; G. Gupta; G. Peng; V. Jehová González; I.J. Janica; V. Fuster Pozo; S. Chortarea; et al. (Toxicology Letters, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

The best linear unbiased prediction (BLUP) method as a tool to estimate the lifetime risk of pancreatic ductal adenocarcinoma in high-risk individuals with no known pathogenic germline variants - Cristina-Marianini-Rios; María E. Castillo Sanchez; Ana García García de Paredes; Mercedes Rodríguez; Emma Barreto; Jorge Villalón López; Raquel Fuentes; María Muñoz Beltrán; Alfonso Sanjuanbenito; Eduardo Lobo; Alejandra Caminoa; Ignacio Ruz-Caracuel; et al. (Familial Cancer, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-related death in the Western world. The number of diagnosed cases and the mortality rate are almost equal as the majority of patients present with advanced disease at diagnosis. Between 4 and 10% of pancreatic cancer cases have an apparent hereditary background, known as hereditary pancreatic cancer (HPC) and familial pancreatic cancer (FPC), when the genetic basis is unknown. Surveillance of high-risk individuals (HRI) from these families by imaging aims to detect PDAC at an early stage to improve prognosis. However, the genetic basis is unknown in the majority of HRIs, with only around 10–13% of families carrying known pathogenic germline mutations. The aim of this study was to assess an individual’s genetic cancer risk based on sex and personal and family history of cancer. The Best Linear Unbiased Prediction (BLUP) methodology was used to estimate an individual’s predicted risk of developing cancer during their lifetime. The model uses different demographic factors in order to estimate heritability. A reliable estimation of heritability for pancreatic cancer of 0.27 on the liability scale, and 0.07 at the observed data scale as obtained, which is different from zero, indicating a polygenic inheritance pattern of PDAC. BLUP was able to correctly discriminate PDAC cases from healthy individuals and those with other cancer types. Thus, providing an additional tool to assess PDAC risk HRI with an assumed genetic predisposition in the absence of known pathogenic germline mutations.

The Spanish Familial Pancreatic Cancer Registry (PANGENFAM): a decade follow-up of individuals at high-risk for pancreatic cancer - Julie Earl; Raquel Fuentes; María E. Castillo Sanchez; Ana García García de Paredes; María Muñoz; Alfonso Sanjuanbenito; Eduardo Lobo; Alejandra Caminoa; Mercedes Rodríguez; Emma Barreto; Jorge Villalón López; Ignacio Ruz-Caracuel; et al. (Familial Cancer, 2024)
The Spanish Familial Pancreatic Cancer Registry (PANGENFAM) was established in 2009 and aims to characterize the genotype and phenotype of familial pancreatic cancer (FPC). Furthermore, an early detection screening program for pancreatic ductal adenocarcinoma (PDAC) is provided to healthy high-risk individuals from FPC and hereditary pancreatic cancer families (first-degree relatives). This article describes our experience over the last 10 years in high-risk screening. Hereditary and familial pancreatic cancer families were identified through the oncology and gastroenterology units. High-risk individuals underwent annual screening with endoscopic ultrasound (EUS) and magnetic resonance (MRI) from age 40 or 10 years younger than the youngest affected family member. Results: PANGENFAM has enrolled 290 individuals from 143 families, including 52 PDAC cases and 238 high-risk individuals. All high-risk individuals eligible for screening were offered to enter the surveillance program, with 143 currently participating. Pancreatic abnormalities were detected in 94 individuals (median age 53 years (29–83), with common findings including cystic lesions and inhomogeneous parenchyma. Imaging test concordance was 66%. Surgical intervention was performed in 4 high-risk individuals following highly suspicious lesions detected by imaging. PANGENFAM is a valuable resource for science innovation, such as biobanking, with clinical and imaging data available for analysis. For high-risk families, it may offer a potential for early diagnosis. Collaboration with other national and international registries is needed to increase our understanding of the disease biology and to standardize criteria for inclusion and follow-up, optimizing cost-effectiveness and efficacy.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Correction: Water stress decreases the biocontrol efficacy of a nucleopolyhedrovirus against the fall armyworm on maize - Raúl Omar Real‑Santillán; Ek del‑Val; Trevor Williams; Ana Mabel Martínez‑Castillo; Mayra E. Gavito; Hexon Angel Contreras-Cornejo; Tsiri Díaz; Griselda García‑Gómez; John Larsen (Journal of Pest Science, 2024)

Water stress decreases the biocontrol efficacy of a nucleopolyhedrovirus against the fall armyworm on maize - Raúl Omar Real-Santillán; Ek del-Val; Trevor Williams; Ana Mabel Martínez-Castillo; Mayra E. Gavito; Hexon Ángel Contreras-Cornejo; Tsiri Díaz; Griselda García-Gómez; John Larsen (Journal of Pest Science, 2024)
Drought events are expected to limit crop productivity in the context of current climate change. Drought is also likely to affect multitrophic interactions such as those involving plants, phytophagous insects and their natural enemies. We designed a two-phase experiment to test the effect of water availability and fertilizer treatment on the interaction between maize, the fall armyworm and its nucleopolyhedrovirus pathogen. Plants grown in soil with high irrigation and mineral fertilization had the highest shoot and root dry weight. Furthermore, plant nitrogen levels were higher in plants with fertilization and a low irrigation scheme compared to other treatments. Low irrigation of maize plants reduced virus-induced mortality of armyworm larvae. Insects did not feed on plants with high irrigation and without fertilization. We conclude that water stress and plant nutrition can affect virus performance and thereby affect the efficiency of biological control and pest management, especially as water and nutrient limitation will likely increase under climate change.

Prophages carrying Zot toxins on different Vibrio genomes: A comprehensive assessment using multilayer networks - Esteban F. Soto; Melissa Alegría; Felipe Sepúlveda; Katherine García; Gastón Higuera; Daniel Castillo; Francisco E. Fontúrbel; Roberto Bastías (Environmental Microbiology, 2024)
Vibrios, a group of bacteria that are among the most abundant in marine environments, include several species such as Vibrio cholerae and Vibrio parahaemolyticus , which can be pathogenic to humans. Some species of Vibrio contain prophages within their genomes. These prophages can carry genes that code for toxins, such as the zonula occludens toxin (Zot), which contribute to bacterial virulence. Understanding the association between different Vibrio species, prophages and Zot genes can provide insights into their ecological interactions. In this study, we evaluated 4619 Vibrio genomes from 127 species to detect the presence of prophages carrying the Zot toxin. We found 2030 potential prophages with zot ‐like genes in 43 Vibrio species, showing a non‐random association within a primarily modular interaction network. Some prophages, such as CTX or Vf33, were associated with specific species. In contrast, prophages phiVCY and VfO3K6 were found in 28 and 20 Vibrio species, respectively. We also identified six clusters of Zot‐like sequences in prophages, with the ZOT2 cluster being the most frequent, present in 34 Vibrio species. This analysis helps to understand the distribution patterns of zot ‐containing prophages across Vibrio genomes and the potential routes of Zot‐like toxin dissemination.

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Hg and Se in Muscle and Liver of Blue Shark (Prionace glauca) from the Entrance of the Gulf of California: An Insight to the Potential Risk to Human Health - M. E. Rechimont; J. Ruelas-Inzunza; F. Amezcua; F. Paéz-Osuna; J. L. Castillo-Géniz (Archives of Environmental Contamination and Toxicology, 2024)

Assessment of Shoreline Change from SAR Satellite Imagery in Three Tidally Controlled Coastal Environments - Salvatore Savastano; Paula Gomes da Silva; Jara Martínez Sánchez; Arnau Garcia Tort; Andres Payo; Mark E. Pattle; Albert Garcia-Mondéjar; Yeray Castillo; Xavier Monteys (Journal of Marine Science and Engineering, 2024)
Coasts are continually changing and remote sensing from satellites has the potential to both map and monitor coastal change at multiple scales. Unlike optical technology, synthetic aperture radar (SAR) is uninfluenced by darkness, clouds, and rain, potentially offering a higher revision period to map shoreline position and change, but this can only be feasible if we have a better interpretation of what shorelines as extracted from SAR imagery represent on the ground. This study aims to assess the application of shorelines extracted from SAR from publicly available satellite imagery to map and capture intra-annual to inter-annual shoreline variability. This is assessed in three tidally controlled coastal study areas that represent sand and gravel beaches with different backshore environments: low-lying dunes and marsh; steep, rocky cliff; and urban environments. We have found that SAR shorelines consistently corresponded to positions above the high-water mark across all three sites. We further discuss the influence of the scene geometry, meteorological and oceanographic conditions, and backshore environment and provide a conceptual interpretation of SAR-derived shorelines. In a low-lying coastal setting, the annual change rate derived through SAR presents a high degree of alignment with the known reference values. The present study contributes to our understanding of the poorly known aspect of using shorelines derived from publicly available SAR satellite missions. It outlines a quantitative approach to automatically assess their quality with a new automatic detection method that is transferable to shoreline evolution assessments worldwide.

Are remote rural areas in Europe remarkable? Challenges and opportunities - Carolina Perpiña Castillo; Ricardo Ribeiro Barranco; Riccardo Curtale; Mert Kompil; Chris Jacobs-Crisioni; Sara Vallecillo Rodriguez; Jean-Philippe Aurambout; Filipe Batista e Silva; Patrizia Sulis; Davide Auteri (Journal of Rural Studies, 2024)

Assessing space and time changes in daily maximum temperature in the Ebro basin (Spain) using model‐based statistical tools - Ana C. Cebrián; Jesús Asín; Jorge Castillo‐Mateo; Alan E. Gelfand; Jesús Abaurrea (International Journal of Climatology, 2023)
There is continuing interest in the investigation of change in temperature over space and time. For this analysis, we offer statistical tools to illuminate changes temporally, at desired temporal resolution, and spatially, using data generated from suitable space–time models. The proposed tools can be used with the output from any suitable model fitted to any set of spatially referenced time series data. The tools to assess space and time changes include spatial surfaces of probabilities and spatial extents for events defined by exceeding a threshold. The spatial surfaces capture the spatial variation in the probability or risk of an exceedance event, while the spatial extents capture the expected proportion of incidence of an event for a region of interest. This approach is used analyse the changes in daily maximum temperature in an inland Mediterranean region (NE of Spain) in the period 1956–2015. The area is very heterogeneous in orography and climate, including the central Ebro valley and part of the Pyrenees. We use a collection of daily temperature series obtained from simulation under a Bayesian daily temperature model fitted to 18 stations in that area. The results for the summer period show that, although there is an increasing risk in all the events used to quantify the effects of climate change, it is not spatially homogeneous, with the largest increase arising in the centre of the Ebro valley and the Eastern Pyrenees area. The risk of an increase in the average daily maximum temperature from 1966–1975 to 2006–2015 higher than 1°C is higher than 0.5 over all of the region, and close to 1 in the previous areas. The extent of daily maximum temperature higher than the reference mean has increased 3.5% per decade. The mean of the extent indicates that 95% of the area under study has suffered a positive increment of the average temperature, and almost 70% an increment higher than 1°C.

Leaching tests reveal fast aluminum fluoride release from ashfall accumulated in La Palma (Canary Islands, Spain) after the 2021 Tajogaite eruption - J. Sánchez-España; M. Pilar Mata; J. Vegas; G. Lozano; J. Mediato; J. Martínez Martínez; I. Galindo; N. Sánchez; B. del Moral; B. Ordóñez; A. de Vergara; A. Nieto; et al. (Journal of Volcanology and Geothermal Research, 2023)

Assessing earlywood-latewood proportion influence on tree-ring stable isotopes - M.C.A. Torbenson; U. Büntgen; P. Römer; O. Urban; M. Trnka; A. Ač; F. Reinig; M. Rybníček; T. Kolář; T. Arosio; E. Martinez del Castillo; E. Koňasová; et al. (Dendrochronologia, 2023)

Tracking the permeation of PVS2 components in living Mentha x Piperita SHOOT TIPS USING OPTICAL MICROSCOPIES - Heidi D. Kreckel; Albert Ochoa Castillo; Remi Bonnart; Gayle M. Volk; Dominik Stich; Nancy E. Levinger (Cryobiology, 2023)

Space-time multi-level modeling for zooplankton abundance employing double data fusion and calibration - Jorge Castillo-Mateo; Alan E. Gelfand; Christine A. Hudak; Charles A. Mayo; Robert S. Schick (Environmental and Ecological Statistics, 2023)
An important objective for marine biologists is to forecast the distribution and abundance of planktivorous marine predators. To do so, it is critically important to understand the spatiotemporal dynamics of their prey. Here, the prey we study are zooplankton and we build a novel space-time hierarchical fusion model to describe the distribution and abundance of zooplankton species in Cape Cod Bay (CCB), MA, USA. The data were collected irregularly in space and time at sites within the first half of the year over a 17 year period, using two different sampling methods. We focus on sea surface zooplankton abundance and incorporate sea surface temperature as a primary driver, also collected with two different sampling methods. So, with two sources for each, we observe true abundance or true sea surface temperature with measurement error. To account for such error, we apply calibrations to align the data sources and use the fusion model to develop a prediction of daily spatial zooplankton abundance surfaces throughout CCB. To infer average abundance on a given day within a given year in CCB, we present a marginalization of the zooplankton abundance surface. We extend the inference to consider abundance averaged to a bi-weekly or annual scale as well as to make an annual comparison of abundance.

Development of healthy synbiotic corn-based snack: Nutritional composition and effect of agave fructan-alginate coating on survival of Lactobacillus acidophilus - Valeria Castillo-Escandón; Gabriela Ramos-Clamont Montfort; Alma Rosa Islas Rubio; Jolanta E. Marszalek; Rodrigo Subiría-Cueto; Silvia Fernández Michel (Journal of Cereal Science, 2023)

Epidemiological features of Leishmania infantum in dogs (Canis lupus familiaris) suggest a latent risk of visceral leishmaniasis in the metropolitan area of Bucaramanga, Santander, Eastern Colombia - Jeiczon Jaimes-Dueñez; Adriana Castillo-Castañeda; Ángela Jiménez-Leaño; Jonny E. Duque; Omar Cantillo-Barraza; Diana Isabel Cáceres-Rivera; Yurany Granada; Omar Triana-Chávez; Juan David Ramírez (Preventive Veterinary Medicine, 2023)

A critical review of textile industry wastewater: green technologies for the removal of indigo dyes - L. A. Castillo-Suárez; A. G. Sierra-Sánchez; I. Linares-Hernández; V. Martínez-Miranda; E. A. Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Binary fluoride and As(V) adsorption in water using pleco fish bone chars - Sergio A. Cruz-Briano; Nahum A. Medellin-Castillo; Pablo Delgado-Sanchez; Guillermo J. Castro-Larragoitia; Roberto Leyva-Ramos; Miguel A. Cortina-Rangel; Gladis J. Labrada-Delgado; Diana E. Villela-Martinez; Alfredo I. Flores-Rojas; Lázaro A. Gonzalez-Fernandez; Hilda G. Cisneros-Ontiveros (Environmental Science and Pollution Research, 2023)

Bacterial communities shift and influence in an acid mine drainage treatment using barium carbonate disperse alkaline substrate system - J. Castillo; J. Alom; A. Gomez-Arias; S. Cebekhulu; A. Matu; E. Cason; A. Valverde (Science of The Total Environment, 2023)

Linking shape and growth in young-of-the-year rockfish: an ecological carry-over effect? - Mauricio F. Landaeta; Anakaren Gómez; Jorge E. Contreras; Yanara Figueroa-González; Elías Pinilla; Pablo Reche; Manuel I. Castillo; Guido Plaza (Marine Biology, 2023)

Treatment processes and analysis of rainwater quality for human use and consumption regulations, treatment systems and quality of rainwater - C Morales-Figueroa; L A Castillo-Suárez; I Linares-Hernández; V Martínez-Miranda; E A Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

Understanding the landscape evolution of El Mogote barrier spit, Baja California Sur, Mexico, using OSL dating, satellite images and a multivariate analysis - A. Valoix; E. Muñoz-Salinas; M. Castillo; D. Sanderson; A. Cresswell (Journal of South American Earth Sciences, 2023)

Nucleus incertus projections to rat medial septum and entorhinal cortex: rare collateralization and septal-gating of temporal lobe theta rhythm activity - Isis Gil-Miravet; Ángel Núñez-Molina; Mónica Navarro-Sánchez; Esther Castillo-Gómez; Francisco Ros-Bernal; Andrew L. Gundlach; Francisco E. Olucha-Bordonau (Brain Structure and Function, 2023)
Nucleus incertus (NI) neurons in the pontine tegmentum give rise to ascending forebrain projections and express the neuropeptide relaxin-3 (RLN3) which acts via the relaxin-family peptide 3 receptor (RXFP3). Activity in the hippocampus and entorhinal cortex can be driven from the medial septum (MS), and the NI projects to all these centers, where a prominent pattern of activity is theta rhythm, which is related to spatial memory processing. Therefore, we examined the degree of collateralization of NI projections to the MS and the medial temporal lobe (MTL), comprising medial and lateral entorhinal cortex (MEnt, LEnt) and dentate gyrus (DG), and the ability of the MS to drive entorhinal theta in the adult rat. We injected fluorogold and cholera toxin-B into the MS septum and either MEnt, LEnt or DG, to determine the percentage of retrogradely labeled neurons in the NI projecting to both or single targets, and the relative proportion of these neurons that were RLN3-positive ( +). The projection to the MS was threefold stronger than that to the MTL. Moreover, a majority of NI neurons projected independently to either MS or the MTL. However, RLN3 + neurons collateralize significantly more than RLN3-negative (–) neurons. In in vivo studies, electrical stimulation of the NI induced theta activity in the MS and the entorhinal cortex, which was impaired by intraseptal infusion of an RXFP3 antagonist, R3(BΔ23-27)R/I5, particularly at ~ 20 min post-injection. These findings suggest that the MS plays an important relay function in the NI-induced generation of theta within the entorhinal cortex.

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Bone appétit: DNA metabarcoding as a non-lethal alternative to morphological dietary assessment in Atlantic bonefish (Albula vulpes) - Lewis J. Campbell; Nicholas A. Castillo; Jonathan Shenker; Leah A. Owens; Rolando O. Santos; Aaron J. Adams; Jennifer S. Rehage; Kate E. Denton; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Using recreational tournament records to construct a 53-year time series of the Florida Keys recreational Bonefish fishery - Ross E. Boucek; Jennifer S. Rehage; Nicholas A. Castillo; Elijah Dwoskin; Steven M. Lombardo; Rolando Santos; Carl Navarre; Michael Larkin; Aaron J. Adams (Environmental Biology of Fishes, 2023)

A review of estimation methods for natural mortality and their performance in the context of fishery stock assessment - Mark N. Maunder; Owen S. Hamel; Hui-Hua Lee; Kevin R. Piner; Jason M. Cope; André E. Punt; James N. Ianelli; Claudio Castillo-Jordán; Maia S. Kapur; Richard D. Methot (Fisheries Research, 2023)

Slow and steady hurts the crab: Effects of chronic and acute microplastic exposures on a filter feeder crab - Mauricio A. Urbina; Caroline da Silva Montes; Angela Schäfer; Nicole Castillo; Ángel Urzúa; Marcelo E. Lagos (Science of The Total Environment, 2023)

Hydrogeochemical and isotopic signatures elucidate deep subsurface hypersaline brine formation through radiolysis driven water-rock interaction - D.M. Nisson; T.L. Kieft; H. Drake; O. Warr; B. Sherwood Lollar; H. Ogasawara; S.M. Perl; B.M. Friefeld; J. Castillo; M.J. Whitehouse; E. Kooijman; T.C. Onstott (Geochimica et Cosmochimica Acta, 2023)

Guayule bagasse to make mycelium composites: An alternative to enhance the profitability of a sustainable guayule crop - E. César; M.A. Castillo-Campohermoso; A.S. Ledezma-Pérez; L.A. Villarreal-Cárdenas; L. Montoya; V.M. Bandala; A.M. Rodríguez-Hernández (Biocatalysis and Agricultural Biotechnology, 2023)

Molecular diagnostics of the Mediterranean olive cyst nematode, Heterodera mediterranea Vovlas, Inserra & Stone, 1981 using conventional and real-time PCR - Sergei A. Subbotin; Julie Burbridge; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2023)

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Integrated evidence‐based extent of occurrence for North American bison ( Bison bison ) since 1500 CE and before - Jeff M. Martin; Rachel A. Short; Glenn E. Plumb; Lauren Markewicz; Dirk H. Van Vuren; Bradly Wehus‐Tow; Erik Otárola‐Castillo; Matthew E. Hill (Ecology, 2023)
Following the near extinction of bison ( Bison bison ) from its historic range across North America in the late 19th century, novel bison conservation efforts in the early 20th century catalyzed a popular widespread conservation movement to protect and restore bison among other species and places. Since Allen's initial delineation (1876) of the historic distribution of North American bison, subsequent attempts have been hampered by knowledge gaps about bison distribution and abundance prior to and following colonial arrival and settlement. For the first time, we applied a multidisciplinary approach to assemble a comprehensive, integrated geographic database and meta‐analysis of bison occurrence over the last 200,000 years, with particular emphasis on the 450 years before present. We combined paleontology, archaeology, and historical ecology data for our database, which totaled 6438 observations. We derived the observations from existing online databases, published literature, and first‐hand exploration journal entries. To illustrate the conservative maximum historical extent of occurrence of bison, we created a concave hull using observations occurring over the last 450 years ( n = 3379 observations), which is the broadly accepted historical benchmark at 1500 CE covering 59% of the North American continent. Although this distribution represents a historic extent of occurrence—merely delineating the maximum margins of the near‐continental distribution—it does not replace a density‐based approach reconstructing potential historical range distributions, which identifies core and marginal ranges. However, we envision the observations contained in this database will contribute to further research in the increasingly evidence‐based disciplines of bison ecology, evolution, rewilding, management, and conservation. There are no copyright or proprietary restrictions on these data, and this data paper should be cited when the data are reused.

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

Molecular diversity of Radopholus similis (Cobb 1913) Thorne (1949) (Nematoda: Pratylenchidae) affecting banana from Costa Rica - Pedro E. Torres; Rafael Segura; Jorge Sandoval; Carolina Cantalapiedra-Navarrete; Ilenia Clavero-Camacho; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2022)

Predicted threats to a native squirrel from two invading species based on citizen science data - Theodore T. Tran; Benjamin E. Carter; Jessica A. Castillo Vardaro (Biological Invasions, 2022)

Cytotoxic and antiproliferative activity of thiazole derivatives of Ochraceolide A - Angel D. Herrera-España; Jenner Us-Martín; Carlos Quintal-Novelo; Gumersindo Mirón-López; Ramiro F. Quijano-Quiñones; David Cáceres-Castillo; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Natural Product Research, 2022)

Spatio-temporal analysis of the extent of an extreme heat event - Ana C. Cebrián; Jesús Asín; Alan E. Gelfand; Erin M. Schliep; Jorge Castillo-Mateo; María A. Beamonte; Jesús Abaurrea (Stochastic Environmental Research and Risk Assessment, 2022)
Evidence of global warming induced from the increasing concentration of greenhouse gases in the atmosphere suggests more frequent warm days and heat waves. The concept of an extreme heat event (EHE), defined locally based on exceedance of a suitable local threshold, enables us to capture the notion of a period of persistent extremely high temperatures. Modeling for extreme heat events is customarily implemented using time series of temperatures collected at a set of locations. Since spatial dependence is anticipated in the occurrence of EHE’s, a joint model for the time series, incorporating spatial dependence is needed. Recent work by Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) develops a space-time model based on a point-referenced collection of temperature time series that enables the prediction of both the incidence and characteristics of EHE’s occurring at any location in a study region. The contribution here is to introduce a formal definition of the notion of the spatial extent of an extreme heat event and then to employ output from the Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) modeling work to illustrate the notion. For a specified region and a given day, the definition takes the form of a block average of indicator functions over the region. Our risk assessment examines extents for the Comunidad Autónoma de Aragón in northeastern Spain. We calculate daily, seasonal and decadal averages of the extents for two subregions in this comunidad. We generalize our definition to capture extents of persistence of extreme heat and make comparisons across decades to reveal evidence of increasing extent over time.

Mixed-Mode Fracture Modelling of the Near-Wellbore Interaction Between Hydraulic Fracture and Natural Fracture - Xun Xi; Zoe K. Shipton; Jackie E. Kendrick; Andrew Fraser‑Harris; Julien Mouli-Castillo; Katriona Edlmann; Christopher I. McDermott; Shangtong Yang (Rock Mechanics and Rock Engineering, 2022)
The interaction between hydraulic fractures (HF) and natural fractures (NF) is one of the most fundamental phenomena in hydraulic fracturing. The near-wellbore interaction between HF and NF significantly affects fracking-related operations including the injected fluid flow, proppant transport and well productivity. However, the nature of fracturing modes, combined with hydro-mechanical coupling, poses great difficulties and challenges in addressing this problem. Literature review suggests that little research has been undertaken on near-wellbore interaction, especially considering the fully coupled hydro-mechanical mixed-mode fracturing process. This paper develops a new fracture model incorporating the Mohr–Coulomb criterion with the cohesive crack model. The model is implemented into ABAQUS solver by in-house FORTRAN subroutines. The rock matrix and cohesive crack interfaces are both coupled with fluid flow. The developed model is then validated by comparing the results with analytical solutions and experimental results. Moreover, the effects of approach angle, NF location, in situ stress, cohesion strength and friction angle of NF, and flow rate on the near-wellbore interaction are investigated. Three interaction modes, i.e., cross, deflect and offset, are reproduced through the numerical method. The crack deflection into NF is a shear-dominated mixed-mode fracture. A high injection pressure in the wellbore tends to drive the HF to cross a NF located close to the wellbore. The smaller the cohesion strength and friction angle of NF is, the larger the offsetting ratio is. A low injection flow rate can help activate natural fractures near the wellbore when intersected by HF.

Elucidating historical fisheries’ networks in the Iberian Peninsula using stable isotopes - Laura Llorente‐Rodríguez; Oliver E. Craig; André Carlo Colonese; Matthew von Tersch; Eufrasia Roselló‐Izquierdo; Eduardo González Gómez de Agüero; Carlos Fernández‐Rodríguez; Juan Antonio Quirós‐Castillo; Begoña López‐Arias; Ricard Marlasca‐Martín; James Nottingham; Arturo Morales Muñiz (Fish and Fisheries, 2022)
Processed fish is known to have been systematically traded in Europe since the Early Middle Ages to meet increasing demand of incipient markets and religious precepts, yet specific details regarding the supply of different fish in Southern Europe is often missing. Here, we address this gap through an integrated approach involving bone metrics and stable isotopic analysis of archaeological European hake ( Merluccius merluccius , Merluccidae) from the Iberian Peninsula. The results offer new insights regarding historical fisheries production systems, including the regions exploited and commercial routes, whilst also revealing biological differences between archaeological and present‐day hake populations in the North‐east Atlantic and the Mediterranean Sea. This research highlights the fruitful result of combining ichthyoarchaeological and historical data for tracking down the origin and development of historical fisheries in south‐western Europe and their bearing on modern fisheries.

Morphological and molecular characterisation of Longidorus sabalanicus n. sp. (Nematoda: Longidoridae) from Iran - Mohsen Asgari; Ali Eskandari; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2022)

Small Differences in Diet Facilitate the Coexistence of Three Forage Fish Species in an Inshore Northern Patagonian Habitat - Lauren E. Wiesebron; Leonardo R. Castro; Samuel Soto; Jorge Castillo (Frontiers in Marine Science, 2022)
Forage fish play the crucial role of transferring energy from lower to upper trophic levels. These small pelagic fish feed on plankton and can compete with each other for food, leading to potentially complex interactions. Three forage fish species ( Sprattus fuegensis , Strangomera bentincki , and Engraulis ringens ) are commonly found in the inshore waters of Northern Chilean Patagonia, a region with large spatial variability in oceanographic conditions and in the zooplankton community. To better understand what factors may explain coexistence among these three forage fish species, we examined differences in resource availability (zooplankton community and abundances) in three locations (Chiloé, Cordillera, and Aysén regions) within Northern Patagonia. We compared the diet of the three fish species using both stable isotope and stomach content analyses, and we measured their gill rakers. S. fuegensis , the only species found in all three regions, had flexible diets which lent it greater success than the other two species at foraging in waters with fewer prey. We found little diet differentiation among the three species in the copepod-rich Cordillera region, but the diverging diets of S. bentincki and S. fuegensis in the copepod-poor Chiloé region suggest that diet partitioning in areas with fewer resources is due to competition. The small differences in diet facilitates coexistence among the three species, which may help explain the lack of correlation between the three species’ population abundances in the Cordillera region over the past 6 years. Finally, our results show that the high degree of oceanographic heterogeneity in Northern Patagonia may encourage species separation based on their specific environmental requirements.

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Taxonomy update for the family Alphasatellitidae: new subfamily, genera, and species - Arvind Varsani; Darren P. Martin; John W. Randles; H. Josef Vetten; John E. Thomas; Elvira Fiallo-Olivé; Jesús Navas-Castillo; Jean-Michel Lett; F. Murilo Zerbini; Philippe Roumagnac; Bruno Gronenborn (Archives of Virology, 2021)

Identification and characterization of a new cry-like gene found in a Bacillus cereus strain - J. Francisco Castillo-Esparza; Javier Luévano-Borroel; Jorge E. Ibarra (Antonie van Leeuwenhoek, 2021)

Antibodies induced by oral immunization of mice with a recombinant protein produced in tobacco plants harboring Bordetella pertussis epitopes - Karla Sanchez-Alvarez; Sergio Rosales-Mendoza; Karen L. Reyes-Barrera; Leticia Moreno-Fierros; Ruth E. Soria-Guerra; Rosalba Castillo-Collazo; Elizabeth Monreal-Escalente; Angel G. Alpuche-Solis (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Molecular data reveal a structured puma (Puma concolor) population in northern Patagonia, Argentina - Orlando Gallo; Diego F. Castillo; Raquel Godinho; Matías E. Mac Allister; Gabriela P. Fernández; Mauricio Failla; Emma B. Casanave (Mammalian Biology, 2021)

Phylogeography of Habia fuscicauda (Cardinalidae) indicates population isolation, genetic divergence and demographic changes during the Quaternary climate shifts in the Mesoamerican rainforest - Vicente de J. Castillo-Chora; Luz E. Zamudio-Beltrán; Carmen Pozo; Blanca E. Hernández-Baños (Journal of Ornithology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Whole-genome sequencing identifies functional noncoding variation in SEMA3C that cosegregates with dyslexia in a multigenerational family - Amaia Carrion-Castillo; Sara B. Estruch; Ben Maassen; Barbara Franke; Clyde Francks; Simon E. Fisher (Human Genetics, 2021)
Dyslexia is a common heritable developmental disorder involving impaired reading abilities. Its genetic underpinnings are thought to be complex and heterogeneous, involving common and rare genetic variation. Multigenerational families segregating apparent monogenic forms of language-related disorders can provide useful entrypoints into biological pathways. In the present study, we performed a genome-wide linkage scan in a three-generational family in which dyslexia affects 14 of its 30 members and seems to be transmitted with an autosomal dominant pattern of inheritance. We identified a locus on chromosome 7q21.11 which cosegregated with dyslexia status, with the exception of two cases of phenocopy (LOD = 2.83). Whole-genome sequencing of key individuals enabled the assessment of coding and noncoding variation in the family. Two rare single-nucleotide variants (rs144517871 and rs143835534) within the first intron of the SEMA3C gene cosegregated with the 7q21.11 risk haplotype. In silico characterization of these two variants predicted effects on gene regulation, which we functionally validated for rs144517871 in human cell lines using luciferase reporter assays. SEMA3C encodes a secreted protein that acts as a guidance cue in several processes, including cortical neuronal migration and cellular polarization. We hypothesize that these intronic variants could have a cis -regulatory effect on SEMA3C expression, making a contribution to dyslexia susceptibility in this family.

Exposure duration modulates the response of Caribbean corals to global change stressors - Hannah E. Aichelman; Colleen B. Bove; Karl D. Castillo; Jessica M. Boulton; Alyssa C. Knowlton; Olivia C. Nieves; Justin B. Ries; Sarah W. Davies (Limnology and Oceanography, 2021)
Global change, including rising temperatures and acidification, threatens corals globally. Although bleaching events reveal fine‐scale patterns of resilience, traits enabling persistence under global change remain elusive. We conducted a 95‐d controlled‐laboratory experiment investigating how duration of exposure to warming (~28, 31°C), acidification ( p CO 2 ~ 343 [present day], ~663 [end of century], ~3109 [extreme] μ atm), and their combination influences physiology of reef‐building corals ( Siderastrea siderea , Pseudodiploria strigosa ) from two reef zones on the Belize Mesoamerican Barrier Reef System. Every 30 d, net calcification rate, host protein and carbohydrate, chlorophyll a , and symbiont density were quantified for the same coral individual to characterize acclimation potential under global change. Coral physiologies of the two species were differentially affected by stressors and exposure duration was found to modulate these responses. Siderastrea siderea exhibited resistance to end of century p CO 2 and temperature stress, but calcification was negatively affected by extreme p CO 2 . However, S. siderea calcification rates remained positive after 95 d of extreme p CO 2 conditions, suggesting acclimation. In contrast, P. strigosa was more negatively influenced by elevated temperatures, which reduced most physiological parameters. An exception was nearshore P. strigosa , which maintained calcification rates under elevated temperature, suggesting local adaptation to the warmer environment of their natal reef zone. This work highlights how tracking coral physiology across various exposure durations can capture acclimatory responses to global change stressors.

Assisted phytoremediation of lead contaminated soil using Atriplex halimus and its effect on some soil physical properties - E. Acuña; B. Castillo; M. Queupuan; M. Casanova; Y. Tapia (International Journal of Environmental Science and Technology, 2021)

Freshwater pearl culture in Mexico: historic context, present status and future perspectives - Pedro E. Saucedo; Héctor Acosta‐Salmón; Douglas McLaurin‐Moreno; Alfonso Castillo‐Domínguez; Carolina E. Melgar‐Valdés; José M. Mazón‐Suástegui (Reviews in Aquaculture, 2021)
We revise the historic context of freshwater pearl culture in Asia, updating the present situation and perspectives of this activity in Mexico, and, possibly, in some Latin American countries. The review is based on the results of ten years of research conducted in southeast Mexico (state of Tabasco) to firstly determine the demography of freshwater mussel stocks and, based on this information, identify a target species with a higher potential for pearl farming: the fatmucket mussel Psoronaias crocodilorum . The main advances relative to the seeding technique for keshi pearl production and composite technique for half‐pearl (mabe) production are detailed and placed under perspective with China, as today's greatest producer of freshwater pearls. After ten years, several cohorts of keshi and mabe pearls have been produced, representing the first of their kind in Latin America. Although the yield and quality of these pearls has gradually been improved, some aspects of the keshi technique (preparation and seeding of the donor's mantle into the host's mantle) still require further optimisation. To promote social development, one of the goals of the project included the involvement of local communities in the manufacture and selling of handcrafts made from the shell. The other goal was to share the main outcomes derived from the keshi and mabe techniques with academics, producers, and government authorities through a series of training workshops aimed to create awareness in the local communities for the potential of freshwater pearl culture in Tabasco as an aquaculture‐based, environmentally friendly and viable model for socioeconomic development.

Does Heat Tolerance Explain Female Polymorphism in Damselflies? - E. Ulises Castillo-Pérez; Angela Nava-Bolaños; Maya Rocha-Ortega; Alex Córdoba-Aguilar (Journal of Insect Behavior, 2021)

Optimization of theoretical maximal quantity of cells to immobilize on solid supports in the rational design of immobilized derivatives strategy - Freddy Castillo-Alfonso; Marcia M. Rojas; Irina Salgado-Bernal; María E. Carballo; Roberto Olivares-Hernández; Jorge González-Bacerio; José M. Guisán; Alberto del Monte-Martínez (World Journal of Microbiology and Biotechnology, 2021)

Machine Learning Based Predictions of Dissolved Oxygen in a Small Coastal Embayment - Manuel Valera; Ryan K. Walter; Barbara A. Bailey; Jose E. Castillo (Journal of Marine Science and Engineering, 2020)
Coastal dissolved oxygen (DO) concentrations have a profound impact on nearshore ecosystems and, in recent years, there has been an increased prevalance of low DO hypoxic events that negatively impact nearshore organisms. Even with advanced numerical models, accurate prediction of coastal DO variability is challenging and computationally expensive. Here, we apply machine learning techniques in order to reconstruct and predict nearshore DO concentrations in a small coastal embayment while using a comprehensive set of nearshore and offshore measurements and easily measured input (training) parameters. We show that both random forest regression (RFR) and support vector regression (SVR) models accurately reproduce both the offshore DO and nearshore DO with extremely high accuracy. In general, RFR consistently peformed slightly better than SVR, the latter of which was more difficult to tune and took longer to train. Although each of the nearshore datasets were able to accurately predict DO values using training data from the same site, the model only had moderate success when using training data from one site to predict DO at another site, which was likely due to the the complexities in the underlying dynamics across the sites. We also show that high accuracy can be achieved with relatively little training data, highlighting a potential application for correcting time series with missing DO data due to quality control or sensor issues. This work establishes the ability of machine learning models to accurately reproduce DO concentrations in both offshore and nearshore coastal waters, with important implications for the ability to detect and indirectly measure coastal hypoxic events in near real-time. Future work should explore the ability of machine learning models in order to accurately forecast hypoxic events.

tRNA ADENOSINE DEAMINASE 3 is required for telomere maintenance in Arabidopsis thaliana - Sreyashree Bose; Ana Victoria Suescún; Jiarui Song; Claudia Castillo-González; Behailu Birhanu Aklilu; Erica Branham; Ryan Lynch; Dorothy E. Shippen (Plant Cell Reports, 2020)

Pseudacanthus alani, a New Species of Mesoamerican Bess Beetles (Coleoptera: Passalidae) of Oaxaca, Mexico and Nomenclatural Notes for the Genus - E R Ariza-Marín; L Jiménez-Ferbans; P Reyes-Castillo (Neotropical Entomology, 2020)

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Sandy Beach Macrofauna of Yucatán State (Mexico) and Oil Industry Development in the Gulf of Mexico: First Approach for Detecting Environmental Impacts - Edlin Guerra-Castro; Gema Hidalgo; Raúl E. Castillo-Cupul; María Muciño-Reyes; Elsa Noreña-Barroso; Jaime Quiroz-Deaquino; Maite Mascaro; Nuno Simoes (Frontiers in Marine Science, 2020)

Development of nuclear microsatellite markers to facilitate germplasm conservation and population genetics studies of five groups of tropical perennial plants with edible fruits and shoots: rambutan (Nephelium lappaceum L.), sapodilla (Manilkara zapota (L.) P. Royen), lychee (Litchi chinensis Sonn.), mangosteen (Garcinia mangostana Linn. and Garcinia cochinchinensis (Lour.) Choisy) and bamboo (Bambusa vulgaris Schrad. ex J.C. Wendl and Guadua angustifolia Kunth) - Renée S. Arias; Linda L. Ballard; Mary V. Duke; Sheron A. Simpson; Xiaofen F. Liu; Valerie A. Orner; Victor S. Sobolev; Brian E. Scheffler; Jaime Martinez-Castillo (Genetic Resources and Crop Evolution, 2020)

Genetic diversity of coffee (Coffea spp.) in Mexico evaluated by using DArTseq and SNP markers - J. L. Spinoso-Castillo; E. Escamilla-Prado; V. H. Aguilar-Rincón; V. Morales Ramos; G. García de los Santos; P. Pérez-Rodríguez; T. Corona-Torres (Genetic Resources and Crop Evolution, 2020)

Eukaryotic plankton communities across reef environments in Bocas del Toro Archipelago, Panamá - Andrea M. Rodas; Rachel M. Wright; Logan K. Buie; Hannah E. Aichelman; Karl D. Castillo; Sarah W. Davies (Coral Reefs, 2020)

Depositional environments and landscapes of the upper Miocene Ipururo Formation at Shumanza, Subandean Zone, northern Peru - Augustin Feussom Tcheumeleu; Séverine Fauquette; Angélica Aliaga Castillo; Camila Martinez; Federico Moreno; Rosa E. Navarrete; Francisco Parra; Frank P. Wesselingh; Rodolfo Salas-Gismondi; Rafael Varas-Malca; Martin Roddaz; Pierre-Olivier Antoine (Palaeobiodiversity and Palaeoenvironments, 2020)

An integrative taxonomic study of the needle nematode complex Longidorus goodeyi Hooper, 1961 (Nematoda: Longidoridae) with description of a new species. - Ruihang Cai; Tom Prior; Bex Lawson; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo; Antonio Archidona-Yuste (European Journal of Plant Pathology, 2020)
Needle nematodes are polyphagous root-ectoparasites parasitizing a wide range of economically important plants not only by directly feeding on root cells, but also by transmitting nepoviruses. This study deciphers the diversity of the complex Longidorus goodeyi through integrative diagnosis method, based on a combination of morphological, morphometrical, multivariate analysis and molecular data. A new Longidorus species, Longidorus panderaltum n. sp. is described and illustrated from a population associated with the rhizosphere of asphodel ( Asphodelus ramosus L.) in southern Spain. Morphologically, L. panderaltum n. sp. is characterized by having a moderately long female body (5.2-7.0 mm), lip region bluntly rounded and slightly offset by a depression with body contour, amphidial pouch with slightly asymmetrical lobes, odontostyle 80.5–101.0 µm long, tail short and conoid rounded. Longidorus panderaltum n. sp. is quite similar to L. goodeyi and L. onubensis in major morphometrics and morphology. However, differential morphology in the tail shape of first-stage juvenile, phylogeny and haplonet analyses indicate they are three distinct valid species. This study defines those three species as members of L. goodeyi complex group and reveals the taxonomical complexity of the genus Longidorus . This L. goodeyi complex group demonstrated that the biodiversity of Longidorus in this region is still not fully clarified.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Synthesis, in vitro antigiardial activity, SAR analysis and docking study of substituted chalcones - David Cáceres-Castillo; Rubén M. Carballo; Ramiro Quijano-Quiñones; Gumersindo Mirón-López; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Medicinal Chemistry Research, 2020)

Combining Isotopic Techniques to Assess Historical Sediment Delivery in a Forest Catchment in Central Chile - C. Bravo-Linares; P. Schuller; A. Castillo; A. Salinas-Curinao; L. Ovando-Fuentealba; E. Muñoz-Arcos; A. Swales; M. Gibbs; G. Dercon (Journal of Soil Science and Plant Nutrition, 2020)

Growth, forage yield and quality of Morus alba L. and Gliricidia sepium (Jacq.) Walp. in mixed and pure fodder bank systems in Yucatan, México - Olivier S. Ramos-Trejo; Jorge R. Canul-Solís; Azucena del R. Alvarado-Canché; Luis E. Castillo-Sánchez; Juan J. Sandoval-Gío; María J. Campos-Navarrete; Angel T. Piñeiro-Vázquez; Alfonso J. Chay-Canul; Fernando Casanova-Lugo (Agroforestry Systems, 2020)

Accumulation of Sulphur in Atriplex nummularia Cultivated in Mine Tailings and Effect of Organic Amendments Addition - Y. Tapia; B. Loch; B. Castillo; E. Acuña; M. Casanova; O. Salazar; P. Cornejo; M. Antilén (Water, Air, & Soil Pollution, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Integrative descriptions and molecular phylogeny of two new needle nematodes of the genus Longidorus (Nematoda: Longidoridae) from Spain - Ruihang Cai; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2020)

Field Performance of Two Methods for Detection of Poliovirus in Wastewater Samples, Mexico 2016–2017 - Concepción F. Estívariz; Elda E. Pérez-Sánchez; Anita Bahena; Cara C. Burns; Howard E. Gary; Herlinda García-Lozano; Gloria Rey-Benito; Silvia Peñaranda; Katy V. Castillo-Montufar; Raúl S. Nava-Acosta; John Scott Meschke; M. Steven Oberste; et al. (Food and Environmental Virology, 2019)

Availability of copper in mine tailings with humic substance addition and uptake by Atriplex halimus - Y. Tapia; M. Casanova; B. Castillo; E. Acuña; J. Covarrubias; M. Antilén; A. Masaguer (Environmental Monitoring and Assessment, 2019)

Nearshore coral growth declining on the Mesoamerican Barrier Reef System - Justin H. Baumann; Justin B. Ries; John P. Rippe; Travis A. Courtney; Hannah E. Aichelman; Isaac Westfield; Karl D. Castillo (Global Change Biology, 2019)
Anthropogenic global change and local stressors are impacting coral growth and survival worldwide, altering the structure and function of coral reef ecosystems. Here, we show that skeletal extension rates of nearshore colonies of two abundant and widespread Caribbean corals ( Siderastrea siderea , Pseudodiploria strigosa ) declined across the Belize Mesoamerican Barrier Reef System (MBRS) over the past century, while offshore coral conspecifics exhibited relatively stable extension rates over the same temporal interval. This decline has caused nearshore coral extension rates to converge with those of their historically slower growing offshore coral counterparts. For both species, individual mass coral bleaching events were correlated with low rates of skeletal extension within specific reef environments, but no single bleaching event was correlated with low skeletal extension rates across all reef environments. We postulate that the decline in skeletal extension rates for nearshore corals is driven primarily by the combined effects of long‐term ocean warming and increasing exposure to higher levels of land‐based anthropogenic stressors, with acute thermally induced bleaching events playing a lesser role. If these declining trends in skeletal growth of nearshore S. siderea and P. strigosa continue into the future, the structure and function of these critical nearshore MBRS coral reef systems is likely to be severely impaired.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Microsatellite markers in Spanish lime (Melicoccus bijugatus Jacq., Sapindaceae), a neglected Neotropical fruit crop - Jaime Martínez-Castillo; Renée S. Arias; Rubén H. Andueza-Noh; Matilde M. Ortiz-García; Brian M. Irish; Brian E. Scheffler (Genetic Resources and Crop Evolution, 2019)

A physiologically-motivated model of cystic fibrosis liquid and solute transport dynamics across primary human nasal epithelia - Florencio Serrano Castillo; Carol A. Bertrand; Michael M. Myerburg; Monica E. Shapiro; Timothy E. Corcoran; Robert S. Parker (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Recent emergence and extinction of the protection of telomeres 1c gene in Arabidopsis thaliana - Callie R. Kobayashi; Claudia Castillo-González; Yulia Survotseva; Elijah Canal; Andrew D. L. Nelson; Dorothy E. Shippen (Plant Cell Reports, 2019)

Evaluation of chromatophores as natural marks for delta smelt: the effects of life-stage and light intensity - Gonzalo C. Castillo; Marade E. Sandford; Tien-Chieh Hung; Wan-Ru Yang; Galen Tigan; Luke Ellison; Joan C. Lindberg; Erwin E. Van Nieuwenhuyse (Environmental Biology of Fishes, 2019)

Transgenerational effects of inter-ploidy cross direction on reproduction and F2 seed development of Arabidopsis thaliana F1 hybrid triploids - Dorota Duszynska; Bjarni Vilhjalmsson; Rosa Castillo Bravo; Sandesh Swamidatta; Thomas E. Juenger; Mark T. A. Donoghue; Aurélie Comte; Magnus Nordborg; Timothy F. Sharbel; Galina Brychkova; Peter C. McKeown; Charles Spillane (Plant Reproduction, 2019)

Parallel Implementation of a PETSc-Based Framework for the General Curvilinear Coastal Ocean Model - Manuel Valera; Mary P. Thomas; Mariangel Garcia; Jose E. Castillo (Journal of Marine Science and Engineering, 2019)
The General Curvilinear Coastal Ocean Model (GCCOM) is a 3D curvilinear, structured-mesh, non-hydrostatic, large-eddy simulation model that is capable of running oceanic simulations. GCCOM is an inherently computationally expensive model: it uses an elliptic solver for the dynamic pressure; meter-scale simulations requiring memory footprints on the order of 10 12 cells and terabytes of output data. As a solution for parallel optimization, the Fortran-interfaced Portable–Extensible Toolkit for Scientific Computation (PETSc) library was chosen as a framework to help reduce the complexity of managing the 3D geometry, to improve parallel algorithm design, and to provide a parallelized linear system solver and preconditioner. GCCOM discretizations are based on an Arakawa-C staggered grid, and PETSc DMDA (Data Management for Distributed Arrays) objects were used to provide communication and domain ownership management of the resultant multi-dimensional arrays, while the fully curvilinear Laplacian system for pressure is solved by the PETSc linear solver routines. In this paper, the framework design and architecture are described in detail, and results are presented that demonstrate the multiscale capabilities of the model and the parallel framework to 240 cores over domains of order 10 7 total cells per variable, and the correctness and performance of the multiphysics aspects of the model for a baseline experiment stratified seamount.

Neuroprotective effect of Mayan medicinal plant extracts against glutamate-induced toxicity - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Jorge A. Rangel-Méndez; Sergio R. Peraza-Sánchez; Daniel Cortés; Iván Velasco; Rosa E. Moo-Puc (Journal of Natural Medicines, 2019)

Pharmacokinetics of two dosing forms of a recrystallized enrofloxacin as hydrochloride dihydrate in tilapia (Oreochromis niloticus × Oreochromis mossambicus) - E Estrada-San Agustín; L Gutiérrez; M Bernad; H Castillo-Juárez; S Sánchez; H Sumano (Aquaculture International, 2019)

Molecular characterization of a new botybirnavirus that infects Botrytis cinerea - Luis Cottet; Christiaan A. Potgieter; Miguel E. Castro; Antonio Castillo (Archives of Virology, 2019)

The role of collectivism in modeling the adoption of renewable energies: a cross-cultural approach - E. Higueras-Castillo; F. J. Liébana-Cabanillas; F. Muñoz-Leiva; S. Molinillo (International Journal of Environmental Science and Technology, 2019)

A New Species of Vindex Kaup (Coleoptera: Scarabaeoidea: Passalidae: Passalinae: Proculini) from Oaxaca, Mexico - E. R. Ariza-Marín; P. Reyes-Castillo; V. Moctezuma; J. L. Sánchez-Huerta (Neotropical Entomology, 2019)

Una Mano Amiga: Pilot Test of a Patient Navigator Program for Southwest New Mexico - Hugo Vilchis; Lynn E. Onstad; Rachel Benavidez; Rebecca Castillo; Nigel Bush; Janet Sanchez; Mary O’Connell; Beti Thompson; Carol M. Moinpour (Journal of Cancer Education, 2019)

Apparent timing of density banding in the Caribbean coral Siderastrea siderea suggests complex role of key physiological variables - B. E. Benson; J. P. Rippe; C. B. Bove; K. D. Castillo (Coral Reefs, 2019)

Surface impurities on giant gypsum crystals from “la Cueva de las Espadas” (Cave of Swords), Naica, Mexico - Isaí Castillo-Sandoval; Luis E. Fuentes-Cobas; Bernardo E. Pérez-Cazares; Hilda E. Esparza-Ponce; María E. Fuentes-Montero; Hiram Castillo-Michel; Diane Eichert; Ignacio Reyes-Cortes; Iván J. Carreño-Márquez; José M. Napoles-Duarte; María E. Montero-Cabrera (Mineralogy and Petrology, 2018)

Realized niche and spatial pattern of native and exotic halophyte hybrids - B. Gallego-Tévar; G. Curado; B. J. Grewell; M. E. Figueroa; J. M. Castillo (Oecologia, 2018)

Corals sustain growth but not skeletal density across the Florida Keys Reef Tract despite ongoing warming - John P. Rippe; Justin H. Baumann; Daphne N. De Leener; Hannah E. Aichelman; Eric B. Friedlander; Sarah W. Davies; Karl D. Castillo (Global Change Biology, 2018)
Through the continuous growth of their carbonate skeletons, corals record information about past environmental conditions and their effect on colony fitness. Here, we characterize century‐scale growth records of inner and outer reef corals across ~200 km of the Florida Keys Reef Tract (FKRT) using skeletal cores extracted from two ubiquitous reef‐building species, Siderastrea siderea and Pseudodiploria strigosa . We find that corals across the FKRT have sustained extension and calcification rates over the past century but have experienced a long‐term reduction in skeletal density, regardless of reef zone. Notably, P. strigosa colonies exhibit temporary reef zone‐dependent reductions in extension rate corresponding to two known extreme temperature events in 1969–1970 and 1997–1998. We propose that the subtropical climate of the FKRT may buffer corals from chronic growth declines associated with climate warming, though the significant reduction in skeletal density may indicate underlying vulnerability to present and future trends in ocean acidification.

Complementary chromatic and far-red photoacclimations in Synechococcus ATCC 29403 (PCC 7335). I: The phycobilisomes, a proteomic approach - Priscila Herrera-Salgado; Lourdes E. Leyva-Castillo; Emmanuel Ríos-Castro; Carlos Gómez-Lojero (Photosynthesis Research, 2018)

Logging Pattern and Landscape Change in Southern Mexico: Identifying Potential Weaknesses and Strengthening Conservation in Community-Based Management Programs through Landscape Analysis - J A Ascanio-Lárraga; J L León-Cortés; M A Castillo-Santiago; E Ramírez-Segura (Journal of Forestry, 2018)

Removal of Two Neonicotinoid Insecticides and Mineralization of 14C-Imidacloprid in Biomixtures - Gabriel Rodríguez-Castillo; Marvin Molina-Rodríguez; Marta Pérez-Villanueva; Mario Masís-Mora; Carlos E. Rodríguez-Rodríguez (Bulletin of Environmental Contamination and Toxicology, 2018)

Dynamic fuzzy neural network for simulating the fixed-bed adsorption of cadmium, nickel, and zinc on bone char - F. A. Gordillo-Ruíz; F. J. Sánchez-Ruíz; D. I. Mendoza-Castillo; H. E. Reynel-Ávila; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2018)

Ecotoxicology in tropical regions - Jonas S. Gunnarsson; Luisa E. Castillo (Environmental Science and Pollution Research, 2018)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

In situ toxicity and ecological risk assessment of agro-pesticide runoff in the Madre de Dios River in Costa Rica - Silvia Echeverría-Sáenz; Freylan Mena; María Arias-Andrés; Seiling Vargas; Clemens Ruepert; Paul J. Van den Brink; Luisa E. Castillo; Jonas S. Gunnarsson (Environmental Science and Pollution Research, 2018)

Environmental risk assessment of pesticides in the River Madre de Dios, Costa Rica using PERPEST, SSD, and msPAF models - Robert A. Rämö; Paul J. van den Brink; Clemens Ruepert; Luisa E. Castillo; Jonas S. Gunnarsson (Environmental Science and Pollution Research, 2018)

Single-cell PCR amplification of thecate dinoflagellates: a case study of Tripos (Dinophyceae) - A. Hernández-Rosas; M. E. Meave del Castillo; J. Díaz-Larrea; F. Rodríguez (Journal of Applied Phycology, 2018)

Integrative diagnosis of carrot cyst nematode (Heterodera carotae) using morphology and several molecular markers for an accurate identification - Mehrdad Madani; Juan E. Palomares-Rius; Nicola Vovlas; Pablo Castillo; Mario Tenuta (European Journal of Plant Pathology, 2018)

Molecular and morphological characterization of the spiral nematode Helicotylenchus oleae Inserra, Vovlas & Golden, 1979 (Nematoda: Hoplolaimidae) in the Mediterranean Basin - Juan E. Palomares-Rius; Carolina Cantalapiedra-Navarrete; Antonio Archidona-Yuste; Nicola Vovlas; Emmanuel A. Tzortzakakis; Pablo Castillo (European Journal of Plant Pathology, 2018)

Areas of endemism persist through time: A palaeoclimatic analysis in the Mexican Transition Zone - Gonzalo E. Pinilla‐Buitrago; Tania Escalante; Ana Gutiérrez‐Velázquez; Pedro Reyes‐Castillo; Octavio R. Rojas‐Soto (Journal of Biogeography, 2018)
Aim The Mexican Transition Zone ( MTZ ) is an area where the Nearctic and Neotropical biogeographical regions overlap, generating high species richness and endemism. The objective of this study was to analyse if potential changes in the composition and the geographical location of areas of endemism (AEs) for beetles and mammals during the Last Glacial Maximum ( LGM ), the mid‐Holocene ( MH ) or the Last Interglacial ( LIG ) have influenced the definition of the MTZ in the present. Location Mexico and Central America. Methods Ecological niche models ( ENM ) were generated describing the current distribution of 218 species associated with the MTZ and then transferred to three periods into the past. A parsimony analysis of endemicity ( PAE ) was run to identify current AE s. The transferred models of each set of species that form the current AE s were used to assess if the geographical ranges of the species’ ecological niches changed over time, or whether they remained stable supporting the validation of the AE s during three past recent periods ( LGM , MH and LIG ). Results Two current AEs were detected that persisted geographically during the three past periods ( LGM , MH and LIG ). Main conclusions The results show that some AEs change through time as a response of climate, whereas others remained stable. Thus, the MTZ could be considered as a dynamic zone at least over the last 130,000 years. The climate analysis of the AEs allows them to be recognized either as true spatio‐temporal units, or as temporarily restricted patterns of co‐distribution resulting from changes in climate over time.

Assessing conservation practices in Amalacaxco Gorge (Izta-Popo National Park, Central Mexico) using fallout 137CS and Optically Stimulated Luminescence (OSL) - E Muñoz-Salinas; M Castillo (Journal of Mountain Science, 2018)

Prevalence and molecular diversity of reniform nematodes of the genus Rotylenchulus (Nematoda: Rotylenchulinae) in the Mediterranean Basin - Juan E. Palomares-Rius; Carolina Cantalapiedra-Navarrete; Antonio Archidona-Yuste; Emmanuel A. Tzortzakakis; Ioannis G. Birmpilis; Nicola Vovlas; Sergei A. Subbotin; Pablo Castillo (European Journal of Plant Pathology, 2018)

Differential Expression of Ion Channels in Adult and Neonatal Rat Ventral Respiratory Column - Celia González-Castillo; Elizabeth Muñoz-Ortiz; Carolina Guzmán-Brambila; Argelia E. Rojas-Mayorquín; Luis Beltran-Parrazal; Daniel Ortuño-Sahagún; Consuelo Morgado-Valle (Journal of Molecular Neuroscience, 2018)

A new dagger nematode, Xiphinema tica n. sp. (Nematoda: Longidoridae), from Costa Rica with updating of the polytomous key of Loof and Luc (1990) - Walter Peraza-Padilla; Carolina Cantalapiedra-Navarrete; Tatiana Zamora-Araya; Juan E. Palomares-Rius; Pablo Castillo; Antonio Archidona-Yuste (European Journal of Plant Pathology, 2018)

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department - J. González del Castillo; A. Julian-Jiménez; F. González-Martínez; J. Álvarez-Manzanares; P. Piñera; C. Navarro-Bustos; M. Martinez-Ortiz de Zarate; F. Llopis-Roca; M. Debán Fernández; J. Gamazo-Del Rio; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of transgenic expression of Brevibacterium linens methionine gamma lyase (MGL) on accumulation of Tylenchulus semipenetrans and key aminoacid contents in Carrizo citrange - Elenor Castillo; Federico Martinelli; Florence Zakharov-Negre; Susan E. Ebeler; Tom R. Buzo; Michael V. McKenry; Abhaya M. Dandekar (Plant Molecular Biology, 2017)

Growth and mortality of larval anchoveta Engraulis ringens , in northern Chile during winter and their relationship with coastal hydrographic conditions - Jorge E. Contreras; Camilo Rodriguez‐Valentino; Mauricio F. Landaeta; Guido Plaza; Manuel I. Castillo; Mónica Alvarado‐Niño (Fisheries Oceanography, 2017)
Larval growth, age, growth effect and instantaneous mortality were estimated in anchoveta, Engraulis ringens , collected biweekly during the austral winter of 2014 in nearshore waters off Bay of Antofagasta (23°41′W–70°30′S), northern Chile. Through measuring standard length ( SL ) and sagitta microstructure analysis, it was estimated that the growth rate of E. ringens larvae decreased from June (0.85 mm day −1 ) to August (0.50 mm day −1 ). However, the water temperature was homogeneous during the sampling dates (14.6, 15.2, 14.4, and 14.6°C), suggesting that the decelerating larval growth was not linked to changes in sea temperature. Additionally, larvae with slow growth have larger otoliths compared with conspecifics with fast growth (growth effect). Larval mortality rates tended to decrease until the middle of July (0.18 per day) but increased to 0.25 per day in early August, which coincided with lower food availability (i.e., chlorophyll‐a, 2.7–5.6 mg m −3 ) and a high occurrence of smaller larvae (1.58–11.5 mm). Partial least squares analysis indicates low covariance between the biological and oceanographic variables ( PLS : 11.71%), suggesting that other factors, such as parental effects, may explain the abrupt decrease in the larval growth rates.

Description and molecular phylogeny of one new and one known needle nematode of the genus Paralongidorus (Nematoda: Longidoridae) from grapevine in Portugal using integrative approach - Carlos Gutiérrez-Gutiérrez; Manuel Mota; Pablo Castillo; Margarida Teixeira Santos; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Host-suitability of black medick (Medicago lupulina L.) and additional molecular markers for identification of the pea cyst nematode Heterodera goettingiana - Alessio Vovlas; Simona Santoro; Vincenzo Radicci; Paola Leonetti; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2017)

Native‐predator–invasive‐prey trophic interactions in Tierra del Fuego: the beginning of biological resistance? - Simón P. Castillo; Ramiro D. Crego; Jaime E. Jiménez; Ricardo Rozzi (Ecology, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Predictive score of haematological toxicity in patients treated with linezolid - J. González-Del Castillo; F. J. Candel; R. Manzano-Lorenzo; L. Arias; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prevalence, geographic distribution and phenotypic differences of Piscirickettsia salmonis EM ‐90‐like isolates - J Saavedra; N Hernandez; A Osses; A Castillo; A Cancino; H Grothusen; E Navas; P Henriquez; H Bohle; F Bustamante; P Bustos; M Mancilla (Journal of Fish Diseases, 2017)
Early reports accounted for two main genotypes of Piscirickettsia salmonis , a fish pathogen and causative agent of piscirickettsiosis, placing the single isolate EM ‐90 apart from the prototypic LF ‐89 and related isolates. In this study, we provide evidence that, contrary to what has been supposed, the EM ‐90‐like isolates are highly prevalent and disseminated across Chilean marine farms. Molecular analysis of 507 P. salmonis field isolates derived from main rearing areas, diverse hosts and collected over 6 years, revealed that nearly 50% of the entire collection were indeed typed as EM ‐90‐like. Interestingly, these isolates showed a marked host preference, being recovered exclusively from Atlantic salmon ( Salmo salar ) samples. Although both strains produce undistinguishable pathological outcomes, differences regarding growth kinetics and susceptibility to the antibiotics and bactericidal action of serum could be identified. In sum, our results allow to conclude that the EM ‐90‐like isolates represent an epidemiologically relevant group in the current situation of piscirickettsiosis. Based on the consistency between genotype and phenotype exhibited by this strain, we point out the need for genotypic studies that may be as important for the Chilean salmon industry as the continuous surveillance of antimicrobial susceptibility patterns.

A simulation tool for advanced design and management of collective sprinkler-irrigated areas: a study case - N. Zapata; E. H. El Malki; B. Latorre; J. Gallinat; F. J. Citoler; R. Castillo; E. Playán (Irrigation Science, 2017)

Molecular characterization of pseudomonodelphic dagger nematodes of the genus Xiphinema Cobb, 1913 (Nematoda: Longidoridae) in Costa Rica, with notes on Xiphinema setariae Tarjan, 1964 - Walter Peraza-Padilla; Antonio Archidona-Yuste; Howard Ferris; Tatiana Zamora-Araya; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Sergei A. Subbotin; Pablo Castillo (European Journal of Plant Pathology, 2017)

A Review of Protist Grazing Below the Photic Zone Emphasizing Studies of Oxygen-Depleted Water Columns and Recent Applications of In situ Approaches - Luis E. Medina; Craig D. Taylor; Maria G. Pachiadaki; Carlos Henríquez-Castillo; Osvaldo Ulloa; Virginia P. Edgcomb (Frontiers in Marine Science, 2017)

Integrative identification and molecular phylogeny of dagger and needle nematodes associated with cultivated olive in Tunisia - Ilhem Guesmi-Mzoughi; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Hajer Regaieg; Najet Horrigue-Raouani; Pablo Castillo (European Journal of Plant Pathology, 2017)

Molecular characterization and distribution of the needle nematode Longidorus laevicapitatus Williams, 1959 (Nematoda: Longidoridae) in Costa Rica - Walter Peraza-Padilla; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Tatiana Zamora-Araya; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2017)

Tamoxifen dosing for Cre-mediated recombination in experimental bronchopulmonary dysplasia - Jordi Ruiz-Camp; José Alberto Rodríguez-Castillo; Susanne Herold; Konstantin Mayer; István Vadász; Michelle D. Tallquist; Werner Seeger; Katrin Ahlbrecht; Rory E. Morty (Transgenic Research, 2017)

A new needle nematode, Longidorus persicus n. sp. (Nematoda: Longidoridae), from Kermanshah province, western Iran - Mehrab Esmaeili; Ramin Heydari; Antonio Archidona-Yuste; Pablo Castillo; Juan E. Palomares-rius (European Journal of Plant Pathology, 2017)

Molecular diversity of bacterial endosymbionts associated with dagger nematodes of the genus Xiphinema (Nematoda: Longidoridae) reveals a high degree of phylogenetic congruence with their host - Juan E. Palomares‐Rius; Antonio Archidona‐Yuste; Carolina Cantalapiedra‐Navarrete; Pilar Prieto; Pablo Castillo (Molecular Ecology, 2016)
Bacterial endosymbionts have been detected in some groups of plant‐parasitic nematodes, but few cases have been reported compared to other groups in the phylum Nematoda, such as animal‐parasitic or free‐living nematodes. This study was performed on a wide variety of plant‐parasitic nematode families and species from different host plants and nematode populations. A total of 124 nematode populations (previously identified morphologically and molecularly) were screened for the presence of potential bacterial endosymbionts using the partial 16S rRNA gene and fluorescence in situ hybridization (FISH) and confocal microscopy. Potential bacterial endosymbionts were only detected in nematode species belonging to the genus Xiphinema and specifically in the X. americanum group. Fifty‐seven partial 16S rRNA sequences were obtained from bacterial endosymbionts in this study. One group of sequences was closely related to the genus ‘ Candidatus Xiphinematobacter’ (19 bacterial endosymbiont sequences were associated with seven nematode host species, including two that have already been described and three unknown bacterial endosymbionts). The second bacterial endosymbiont group (38 bacterial endosymbiont sequences associated with six nematode species) was related to the family Burkholderiaceae , which includes fungal and soil–plant bacterial endosymbionts. These endosymbionts were reported for the first time in the phylum Nematoda. Our findings suggest that there is a highly specific symbiotic relationship between nematode host and bacterial endosymbionts. Overall, these results were corroborated by a phylogeny of nematode host and bacterial endosymbionts that suggested that there was a high degree of phylogenetic congruence and long‐term evolutionary persistence between hosts and endosymbionts.

Extreme 15N Depletion in Seagrasses - M. E. M. Walton; I. Al-Maslamani; N. Haddaway; H. Kennedy; A. Castillo; E. S. Al-Ansari; I. Al-Shaikh; M. Abdel-Moati; M. A. A. Al-Yafei; L. Le Vay (Estuaries and Coasts, 2016)

Acute, chronic and biochemical effects of chlorothalonil on Agalychnis callidryas, Isthmohyla pseudopuma and Smilisca baudinii tadpoles - Michael Méndez; Priscilla Obando; Margaret Pinnock-Branford; Clemens Ruepert; Luisa E. Castillo; Freylan Mena; Gilbert Alvarado (Environmental Science and Pollution Research, 2016)

Root-lesion nematodes of the genus Pratylenchus (Nematoda: Pratylenchidae) from Costa Rica with molecular identification of P. gutierrezi and P. panamaensis topotypes - Tatiana Zamora Araya; Walter Peraza Padilla; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Gracia Liébanas; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2016)

Phenotypic plasticity and population differentiation in response to salinity in the invasive cordgrass Spartina densiflora - Brenda J. Grewell; Jesús M. Castillo; Meghan J. Skaer Thomason; Rebecca E. Drenovsky (Biological Invasions, 2016)

Antioxidant and toxicological evaluation of a Tamarindus indica L. leaf fluid extract - J.C. Escalona-Arranz; R. Perez-Rosés; J. Rodríguez-Amado; H.J. Morris-Quevedo; L.B. Mwasi; O. Cabrera-Sotomayor; R. Machado-García; O. Fong-Lórez; A. Alfonso-Castillo; E. Puente-Zapata (Natural Product Research, 2016)

Rotylenchus cretensis n. sp. and R. cypriensis Antoniou 1980 (Nematoda: Hoplolaimidae) recovered from the rhizosphere of olive at Crete (Greece) with a molecular phylogeny of the genus - Emmanuel A. Tzortzakakis; Antonio Archidona-Yuste; Gracia Liébanas; Ioannis G. Birmpilis; Carolina Cantalapiedra-Navarrete; Juan A. Navas-Cortés; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2016)

Parasitism effects on white clover by root-knot and cyst nematodes and molecular separation of Heterodera daverti from H. trifolii - Nicola Vovlas; Alessio Vovlas; Paola Leonetti; Gracia Liébanas; Pablo Castillo; Sergei A. Subbotin; Juan E. Palomares Rius (European Journal of Plant Pathology, 2015)

A new root-knot nematode Meloidogyne spartelensis n. sp. (Nematoda: Meloidogynidae) in Northern Morocco - Nadine Ali; Johannes Tavoillot; Thierry Mateille; Elodie Chapuis; Guillaume Besnard; Ahmed El Bakkali; Carolina Cantalapiedra-Navarrete; Gracia Liébanas; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2015)

Host reaction of Aloe vera infected by Meloidogyne incognita and M. javanica in Crete Island (Greece) - Juan E. Palomares-Rius; Pablo Castillo; Hava Rapoport; Antonio Archidona-Yuste; Emmanuel A. Tzortzakakis (European Journal of Plant Pathology, 2015)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state - H. M. González-Sánchez; A. Monsiváis-Urenda; C. A. Salazar-Aldrete; A. Hernández-Salinas; D. E. Noyola; M. E. Jiménez-Capdeville; A. Martínez-Serrano; C. G. Castillo (Journal of NeuroVirology, 2015)

Assessment of the risk of failure of high voltage substations due to environmental conditions and pollution on insulators - Rafael Castillo Sierra; Oscar Oviedo-Trespalacios; John E. Candelo; Jose D. Soto (Environmental Science and Pollution Research, 2015)

Management of Perennial Warm-Season Bioenergy Grasses. II. Seasonal Differences in Elephantgrass and Energycane Morphological Characteristics Affect Responses to Harvest Frequency and Timing - Chae-In Na; Lynn E. Sollenberger; John E. Erickson; Kenneth R. Woodard; Miguel S. Castillo; M. Kimberly Mullenix; João M. B. Vendramini; Maria L. Silveira (BioEnergy Research, 2015)

Foraging ecology of silky sharks, Carcharhinus falciformis, captured by the tuna purse-seine fishery in the eastern Pacific Ocean - Leanne M. Duffy; Robert J. Olson; Cleridy E. Lennert-Cody; Felipe Galván-Magaña; Noemi Bocanegra-Castillo; Petra M. Kuhnert (Marine Biology, 2015)

The influence of atmospheric conditions on the leakage current of ceramic insulators on the Colombian Caribbean coast - Rafael Castillo Sierra; Oscar Oviedo-Trespalacios; John E. Candelo; Jose D. Soto (Environmental Science and Pollution Research, 2015)

Secretion of biologically active human interleukin 22 (IL-22) by Lactococcus lactis - María J. Loera-Arias; Julio Villatoro-Hernández; Miguel A. Parga-Castillo; Alejandro Salcido-Montenegro; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Roberto Montes-de-Oca-Luna; Odila Saucedo-Cárdenas (Biotechnology Letters, 2014)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Integrative diagnosis and molecular phylogeny of dagger and needle nematodes of olives and grapevines in the island of Crete, Greece, with description of Xiphinema cretense n. sp. (Nematoda, Longidoridae) - Emmanuel A. Tzortzakakis; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Eleni Nasiou; Maria S. Lazanaki; Emmanouil M. Kabourakis; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2014)

Development of plaque assay for Chilean Infectious Salmon Anaemia Virus, application for virus purification and titration in salmon ASK cells - M T Castillo‐Cerda; L Cottet; D Toro‐Ascuy; E Spencer; M Cortez‐San Martín (Journal of Fish Diseases, 2014)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

How do people perceive urban trees? Assessing likes and dislikes in relation to the trees of a city - Morelia Camacho-Cervantes; Jorge E. Schondube; Alicia Castillo; Ian MacGregor-Fors (Urban Ecosystems, 2014)

Morphological and molecular characterisation of Pratylenchus oleae n. sp. (Nematoda: Pratylenchidae) parasitizing wild and cultivated olives in Spain and Tunisia - Juan E. Palomares-Rius; Ilhem Guesmi; Najet Horrigue-Raouani; Carolina Cantalapiedra-Navarrete; Gracia Liébanas; Pablo Castillo (European Journal of Plant Pathology, 2014)

Biodegradation of organic pollutants in saline wastewater by halophilic microorganisms: a review - Laura C. Castillo-Carvajal; José Luis Sanz-Martín; Blanca E. Barragán-Huerta (Environmental Science and Pollution Research, 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Do Spartina maritima Plantations Enhance the Macroinvertebrate Community in European Salt Marshes? - Guillermo Curado; Juan E. Sánchez-Moyano; Enrique Figueroa; Jesús M. Castillo (Estuaries and Coasts, 2014)

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Microbial diversity in Los Azufres geothermal field (Michoacán, Mexico) and isolation of representative sulfate and sulfur reducers - Elcia M. S. Brito; Norberto Villegas-Negrete; Irene A. Sotelo-González; César A. Caretta; Marisol Goñi-Urriza; Claire Gassie; Florence Hakil; Yannick Colin; Robert Duran; Felix Gutiérrez-Corona; Hilda A. Piñón-Castillo; Germán Cuevas-Rodríguez; et al. (Extremophiles, 2014)

Changes in gene expression patterns associated with microspore embryogenesis in hexaploid triticale (×Triticosecale Wittm.) - I. Żur; E. Dubas; M. Krzewska; R. A. Sánchez-Díaz; A. M. Castillo; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Detection of the camellia root-knot nematode Meloidogyne camelliae Golden in Japanese camellia bonsai imported into Italy: integrative diagnosis, parasitic habits and molecular phylogeny - Nicola Trisciuzzi; Alberto Troccoli; Nicola Vovlas; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2014)

Low dispersive modeling of Rayleigh waves on partly staggered grids - O. Rojas; B. Otero; J. E. Castillo; S. M. Day (Computational Geosciences, 2014)

Native plant restoration combats environmental change: development of carbon and nitrogen sequestration capacity using small cordgrass in European salt marshes - Guillermo Curado; Alfredo E. Rubio-Casal; Enrique Figueroa; Brenda J. Grewell; Jesús M. Castillo (Environmental Monitoring and Assessment, 2013)

Regional signatures of plant response to drought and elevated temperature across a desert ecosystem - Seth M. Munson; Esteban H. Muldavin; Jayne Belnap; Debra P. C. Peters; John P. Anderson; M. Hildegard Reiser; Kirsten Gallo; Alicia Melgoza-Castillo; Jeffrey E. Herrick; Tim A. Christiansen (Ecology, 2013)
The performance of many desert plant species in North America may decline with the warmer and drier conditions predicted by climate change models, thereby accelerating land degradation and reducing ecosystem productivity. We paired repeat measurements of plant canopy cover with climate at multiple sites across the Chihuahuan Desert over the last century to determine which plant species and functional types may be the most sensitive to climate change. We found that the dominant perennial grass, Bouteloua eriopoda , and species richness had nonlinear responses to summer precipitation, decreasing more in dry summers than increasing with wet summers. Dominant shrub species responded differently to the seasonality of precipitation and drought, but winter precipitation best explained changes in the cover of woody vegetation in upland grasslands and may contribute to woody‐plant encroachment that is widespread throughout the southwestern United States and northern Mexico. Temperature explained additional variability of changes in cover of dominant and subdominant plant species. Using a novel empirically based approach we identified “climate pivot points” that were indicative of shifts from increasing to decreasing plant cover over a range of climatic conditions. Reductions in cover of annual and several perennial plant species, in addition to declines in species richness below the long‐term summer precipitation mean across plant communities, indicate a decrease in the productivity for all but the most drought‐tolerant perennial grasses and shrubs in the Chihuahuan Desert. Overall, our regional synthesis of long‐term data provides a robust foundation for forecasting future shifts in the composition and structure of plant assemblages in the largest North American warm desert.

Heterodera elachista the Japanese cyst nematode parasitizing corn in Northern Italy: integrative diagnosis and bionomics - Francesca De Luca; Nicola Vovlas; Giuseppe Lucarelli; Alberto Troccoli; Vincenzo Radicci; Elena Fanelli; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2013)

The PsbO homolog from Symbiodinium kawagutii (Dinophyceae) characterized using biochemical and molecular methods - Raúl E. Castillo-Medina; Tania Islas-Flores; Patricia E. Thomé; Roberto Iglesias-Prieto; Senjie Lin; Huan Zhang; Marco A. Villanueva (Photosynthesis Research, 2013)

Association between individual genetic diversity of two oak host species and canopy arthropod community structure - E. Tovar-Sánchez; L. Valencia-Cuevas; E. Castillo-Mendoza; P. Mussali-Galante; R. V. Pérez-Ruiz; A. Mendoza (European Journal of Forest Research, 2013)

Antibiotic therapy in necrotising external otitis: case series of 32 patients and review of the literature - C. Pulcini; P. Mahdyoun; E. Cua; I. Gahide; L. Castillo; N. Guevara (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Phylogeny, diversity, and species delimitation in some species of the Xiphinema americanum-group complex (Nematoda: Longidoridae), as inferred from nuclear and mitochondrial DNA sequences and morphology - Carlos Gutiérrez-Gutiérrez; Carolina Cantalapiedra-Navarrete; Wilfrida Decraemer; Nicola Vovlas; Tom Prior; Juan E. Palomares Rius; Pablo Castillo (European Journal of Plant Pathology, 2012)

Ecotoxicological characterization of a tropical soil after diazinon spraying - Tiago Natal-da-Luz; Matilde Moreira-Santos; Clemens Ruepert; Luisa E. Castillo; Rui Ribeiro; José Paulo Sousa (Ecotoxicology, 2012)

Time to positivity of blood culture association with clinical presentation, prognosis and ESBL-production in Escherichia coli bacteremia - R. Álvarez; L. Viñas-Castillo; J. A. Lepe-Jiménez; E. García-Cabrera; J. M. Cisneros-Herreros (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Sensory changes related to breeding for plant architecture and resistance to viruses and anthracnose in bean market class Fabada (Phaseolus vulgaris L.) - J. J. Ferreira; Romero R. del Castillo; E. Perez-Vega; M. Plans; J. Simó; F. Casañas (Euphytica, 2012)

E2F1 induces p19INK4d, a protein involved in the DNA damage response, following UV irradiation - Abel L. Carcagno; Luciana E. Giono; Mariela C. Marazita; Daniela S. Castillo; Nicolás Pregi; Eduardo T. Cánepa (Molecular and Cellular Biochemistry, 2012)

Research on arbuscular mycorrhizae in Mexico: an historical synthesis and future prospects - Noé Manuel Montaño; Alejandro Alarcón; Sara Lucía Camargo-Ricalde; Laura Verónica Hernández-Cuevas; Javier Álvarez-Sánchez; Ma. del Carmen A. González-Chávez; Mayra E. Gavito; Irene Sánchez-Gallen; José Ramos-Zapata; Patricia Guadarrama; Ignacio E. Maldonado-Mendoza; Silvia Castillo-Argüero; et al. (Symbiosis, 2012)

The second sodium pump: from the function to the gene - Miguel A. Rocafull; Luz E. Thomas; Jesús R. del Castillo (Pflügers Archiv - European Journal of Physiology, 2012)

Simultaneous detection of the IPN and ISA viruses in outbreaks of clinical disease and mortality in farmed Atlantic salmon, Salmo salar L., in Chile - M Cortez‐San Martin; A Rivas‐Aravena; S Guajardo; M T Castillo; M Jashes; A M Sandino; E Spencer (Journal of Fish Diseases, 2012)

Development of wild barley (Hordeum chilense)-derived DArT markers and their use into genetic and physical mapping - C. Rodríguez-Suárez; M. J. Giménez; N. Gutiérrez; C. M. Ávila; A. Machado; E. Huttner; M. C. Ramírez; A. C. Martín; A. Castillo; A. Kilian; A. Martín; S. G. Atienza (Theoretical and Applied Genetics, 2012)

Regional integration and local change: road paving, community connectivity, and social–ecological resilience in a tri-national frontier, southwestern Amazonia - Stephen G. Perz; Liliana Cabrera; Lucas Araújo Carvalho; Jorge Castillo; Rosmery Chacacanta; Rosa E. Cossio; Yeni Franco Solano; Jeffrey Hoelle; Leonor Mercedes Perales; Israel Puerta; Daniel Rojas Céspedes; Ioav Rojas Camacho; et al. (Regional Environmental Change, 2012)

The Uptake of Copper by Aldama dentata: Ecophysiological Response, Its Modeling, and the Implication for Phytoremediation - N. Dasgupta-Schubert; M. G. Barrera; C. J. Alvarado; O. S. Castillo; E. M. Zaragoza; S. Alexander; S. Landsberger; S. Robinson (Water, Air, & Soil Pollution, 2011)

Isolation of the new anacardic acid 6-[16′Z-nonadecenyl]-salicylic acid and evaluation of its antimicrobial activity against Streptococcus mutans and Porphyromonas gingivalis - Blanca E. Rivero-Cruz; Nuria Esturau; Sobeida Sánchez-Nieto; Irma Romero; Israel Castillo-Juárez; J. Fausto Rivero-Cruz (Natural Product Research, 2011)

Algal assemblages and their relationship with water quality in tropical Mexican streams with different land uses - G. Vázquez; J. A. Aké-Castillo; M. E. Favila (Hydrobiologia, 2011)

Prevalence, polyphasic identification, and molecular phylogeny of dagger and needle nematodes infesting vineyards in southern Spain - Carlos Gutiérrez-Gutiérrez; Juan E. Palomares Rius; Carolina Cantalapiedra-Navarrete; Blanca B. Landa; Pablo Castillo (European Journal of Plant Pathology, 2011)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Role of the Y-Family DNA Polymerases YqjH and YqjW in Protecting Sporulating Bacillus subtilis Cells from DNA Damage - Andrea M. Rivas-Castillo; Ronald E. Yasbin; E. Robleto; Wayne L. Nicholson; Mario Pedraza-Reyes (Current Microbiology, 2010)

Seasonality and anomalies of sea surface temperature off the coast of Nayarit, Mexico - Emilio Palacios-Hernández; Laura E. Carrillo; Anatoliy Filonov; Luis Brito-Castillo; Carlos E. Cabrera-Ramos (Ocean Dynamics, 2010)

Females of a viviparous fish (Skiffia multipunctata) reject males with black colouration - A. Moyaho; P. Guevara-Fiore; E. Beristain-Castillo; C. Macías Garcia (Journal of Ethology, 2010)

Inhibition of mammary tumor growth and metastases to bone and liver by dietary grape polyphenols - Linette Castillo-Pichardo; Michelle M. Martínez-Montemayor; Joel E. Martínez; Kristin M. Wall; Luis A. Cubano; Suranganie Dharmawardhane (Clinical & Experimental Metastasis, 2009)

Impact of extraneous matter on post-harvest sucrose losses and quality parameters in sugarcane - Jesús E. Larrahondo; Edgar F. Castillo; Yuri Peralta; Angélica Jaramillo; Alberto Palma; Carlos Briceño; Fernando Giraldo (Sugar Tech, 2009)

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning - M. D. Pérez-Cárceles; A. Sibón; M. L. Gil del Castillo; M. A. Vizcaya; E. Osuna; T. Casas; J. L. Romero; A. Luna (Biological Trace Element Research, 2008)

High compatibility between arbuscular mycorrhizal fungal communities and seedlings of different land use types in a tropical dry ecosystem - Mayra E. Gavito; Daniel Pérez-Castillo; César F. González-Monterrubio; Teresa Vieyra-Hernández; Miguel Martínez-Trujillo (Mycorrhiza, 2008)

Enhanced duckweed detection using bootstrapped SVM classification on medium resolution RGB MODIS imagery - C. Castillo; I. Chollett; E. Klein (International Journal of Remote Sensing, 2008)

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs - S. Carrillo; E. López; M. M. Casas; E. Avila; R. M. Castillo; M. E. Carranco; C. Calvo; F. Pérez-Gil (Journal of Applied Phycology, 2008)

Physical and chemical limnology of a wind-swept tropical highland reservoir - Martin Merino-Ibarra; Emiliano Monroy-Ríos; Gloria Vilaclara; Fermin S. Castillo; Margarita E. Gallegos; Jorge Ramírez-Zierold (Aquatic Ecology, 2008)

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Arrarás (Immunogenetics, 2008)

Primary and secondary vegetation patches as contributors to floristic diversity in a tropical deciduous forest landscape - Gonzalo Castillo-Campos; Gonzalo Halffter; Claudia E. Moreno (Biodiversity and Conservation, 2008)

Comparative response of bread and durum wheat cultivars to nitrogen fertilizer in a rainfed Mediterranean environment: soil nitrate and N uptake and efficiency - Rafael J. López-Bellido; Juan E. Castillo; Luis López-Bellido (Nutrient Cycling in Agroecosystems, 2008)

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Ararrás (Immunogenetics, 2008)

Suitability of weed species prevailing in Spanish vineyards as hosts for root-knot nematodes - P. Castillo; H. F. Rapoport; J. E. Palomares Rius; R. M. Jiménez Díaz (European Journal of Plant Pathology, 2007)

Plasma Zinc Concentration, Body Composition and Physical Activity in Obese Preschool Children - G. Weisstaub; E. Hertrampf; D. López de Romaña; G. Salazar; C. Bugueño; C. Castillo-Duran (Biological Trace Element Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Identification of Pratylenchus thornei, the cereal and legume root-lesion nematode, based on SCAR-PCR and satellite DNA - S. Carrasco-Ballesteros; P. Castillo; B. J. Adams; E. Pérez-Artés (European Journal of Plant Pathology, 2007)

Contrasting strategies to cope with drought by invasive and endemic species of Lantana in Galapagos - Jesús M. Castillo; Pablo Leira-Doce; Jorge Carrión-Tacuri; Edison Muñoz-Guacho; Aída Arroyo-Solís; Guillermo Curado; David Doblas; Alfredo E. Rubio-Casal; Antonio A. Álvarez-López; Susana Redondo-Gómez; Regina Berjano; Giovanny Guerrero; et al. (Biodiversity and Conservation, 2007)

Regeneration of roots from callus reveals stability of the developmental program for determinate root growth in Sonoran Desert Cactaceae - Svetlana Shishkova; Edith García-Mendoza; Vicente Castillo-Díaz; Norma E. Moreno; Jesús Arellano; Joseph G. Dubrovsky (Plant Cell Reports, 2007)

Complete sequence of the RNA1 of a European isolate of tomato chlorosis virus - G. Lozano; E. Moriones; J. Navas-Castillo (Archives of Virology, 2007)

Introgression in the genus Salmo via allotriploids - A. G. F. CASTILLO; E. BEALL; P. MORAN; J. L. MARTINEZ; F. AYLLON; E. GARCIA‐VAZQUEZ (Molecular Ecology, 2007)
Hybridization between sympatric species is not uncommon in the wild. Wild allotriploids (individuals with two chromosome sets from a species + one chromosome set from another species) are generally the result of a backcross between interspecific hybrids that produce unreduced gametes and one of the parental species. In animals, allotriploids are commonly sterile, except for some vertebrate species complexes in which allotriploids reproduce by parthenogenesis, gynogenesis and/or hybridogenesis, producing generally clonal or hemiclonal gametes; nuclear DNA introgression between hybridizing species is considered to be extremely rare. Employing species‐specific molecular markers, we show genetic introgression between the chromosomally well‐differentiated salmonids Atlantic salmon (2n = 58) and brown trout (2 n = 80) through spontaneous bisexual reproduction of allotriploids leading to salmon‐like offspring bearing some brown trout genes. Although introgression between these Salmo species can occur via allotriploids, we hypothesize that extinction of parental species can be discarded based on very low survival of allotriploid offspring.

Complete nucleotide sequence of the RNA2 of the crinivirus tomato chlorosis virus - G. Lozano; E. Moriones; J. Navas-Castillo (Archives of Virology, 2006)

Climatic cycles inferred from the aminostratigraphy and aminochronology of Quaternary dunes and palaeosols from the eastern islands of the Canary Archipelago - J. E. Ortiz; T. Torres; Y. Yanes; C. Castillo; J. De La Nuez; M. Ibáñez; M. R. Alonso (Journal of Quaternary Science, 2006)
Aminochronological and aminostratigraphical methods have been used to study the Quaternary aeolian deposits from the islands located east of the Canary Archipelago (Fuerteventura and Lanzarote islands and La Graciosa, Montaña Clara and Alegranza islets). The extent of racemisation/epimerisation of four amino acids (isoleucine, aspartic acid, phenylalanine and glutamic acid) was measured in land snail shells of the genus Theba . The age calculation algorithms of these amino acids have been determined to permit the numerical dating of these deposits. Eight Aminozones, each defining dune/palaeosol‐formation episodes, have been distinguished and dated at 48.6 ± 6.4, 42.5 ± 6.0, 37.8 ± 4.6, 29.4 ± 4.8, 22.4 ± 4.5, 14.9 ± 3.6, 11.0 ± 4.0 and 5.4 ± 1.1 ka BP, the first five of them defining cycles of 5–7 ka. The alternation of palaeosols and aeolian deposits, which are related to abrupt transitions from humid to arid conditions, are the reflection of globally induced changes in North Africa palaeoenvironmental conditions linked to the effect of African palaeomonsoons on the trade winds and the Saharan Air Layer. Probably these aeolian cycles, with a recurrence period of 5–7 ka, are the expression of multiples of the ∼2.4 ka solar‐cycle. Copyright © 2005 John Wiley & Sons, Ltd.

Factors Affecting Fertility According to the Postpartum Period in Crossbred Dual-Purpose Suckling Cows in the Tropics - F. Perea-Ganchou; E. Soto Belloso; C. González Stagnaro; G. Soto Castillo; H. Hernández Fonseca (Tropical Animal Health and Production, 2005)

Kinetic Study of the Release of Lead in a Mine-Impacted Tropical River - F. Arcega-Cabrera; S. E. Castillo-Blum; M. A. Armienta (Bulletin of Environmental Contamination and Toxicology, 2005)

Short-term responses to salinity of an invasive cordgrass - Jesús M. Castillo; Alfredo E. Rubio-Casal; Susana Redondo; Antonio A. Álvarez-López; Teresa Luque; Carlos Luque; Francisco J. Nieva; Eloy M. Castellanos; Manuel E. Figueroa (Biological Invasions, 2005)

Growing more rice with less water: Research findings from a study in China - Randoph Barker; To Phuc Tuong; Yuanhua Li; E. G. Castillo; B. A. M. Bouman (Paddy and Water Environment, 2004)

Cryptic isolation of Gulf of California shovelnose guitarfish evidenced by mitochondrial DNA - J. Sandoval-Castillo; A. Rocha-Olivares; C. Villavicencio-Garayzar; E. Balart (Marine Biology, 2004)

Identifying and structurally characterizing CD1b in Aotus nancymaae owl monkeys - Fabio Castillo; Carlos Guerrero; Esperanza Trujillo; Gabriela Delgado; Pilar Martinez; Luz M. Salazar; Paola Barato; Manuel E. Patarroyo; Carlos Parra-Lpez (Immunogenetics, 2004)

Vine species diversity across environmental gradients in northwestern México - Francisco Molina-Freaner; Reyna Castillo Gámez; Clara Tinoco-Ojanguren; Alejandro E. V. Castellanos (Biodiversity and Conservation, 2004)

Ten-Year Viability Study on Natural Populations of Drosophila Sibling Species from Laguna Verde, Veracruz, México - E. Pimentel; M. P. Cruces; V. M. Salceda; M. E. de la Rosa; L. Levine; J. A. Castillo (Archives of Environmental Contamination and Toxicology, 2004)

Insights into Insulin and Glucagon Responses in Fish - I. Navarro; P. Rojas; E. Capilla; A. Albalat; J. Castillo; N. Montserrat; M. Codina; J. Gutiérrez (Fish Physiology and Biochemistry, 2002)

Effects of dietary fish oil on the fatty acid composition of the main lipid classes of chick plasma lipoproteins - M. Castillo; F. Amalik; E. García-Fuentes; E. García-Peregrín (Journal of Physiology and Biochemistry, 2002)

Structure of a pond community in Central Mexico - E. Escobar-Briones; A.M. Cortez-Aguilar; M. García-Ramos; L.M. Mejía-Ortíz; A.Y. Simms-Del Castillo (Hydrobiologia, 2002)

Participatory plant breeding with maize in Mexico and Honduras - Margaret E. Smith; Fernando G. Castillo; Francisco Gómez (Euphytica, 2001)

Multispectral in situ measurements of organic matter and chlorophyll fluorescence in seawater: Documenting the intrusion of the Mississippi River plume in the West Florida Shelf - Carlos E. Del Castillo; Paula G. Coble; Robyn N. Conmy; Frank E. Müller‐Karger; Lisa Vanderbloemen; Gabriel A. Vargo (Limnology and Oceanography, 2001)
We performed multispectral, in situ fluorescence measurements of detrital colored organic matter (COM) and chlorophyll a (Chl a) in surface waters of the West Florida Shelf using the Wet Labs spectral absorption and fluorescence instrument (SAFIre). Continuous underway measurements allowed simultaneous mapping of the dispersal pattern of riverine organic material and Chl a on the shelf. We used two fluorescence emission ratios to differentiate between riverine and marine COM. The data showed unusually high concentrations of COM offshore. These were attributed to an offshore extension of the Mississippi River plume. Comparisons between in situ Chl a concentrations measured with the SAFIre and Chl a values obtained from the sea‐viewing wide field‐of‐view sensor (SeaWiFS) satellite data using OC4 and MODIS algorithms showed that, although both algorithms overestimated Chl a, MODIS performed better than OC4, particularly in areas with high COM concentrations. Analysis of the relationship between Chl a and COM concentrations within the study area showed regional variability probably caused by differences in river source.

Nitrogen pollution by dairy cows and its mitigation by dietary manipulation - E. Kebreab; J. France; D.E. Beever; A.R. Castillo (Nutrient Cycling in Agroecosystems, 2001)

Effect of Pre- and Post-Partum Feed Supplementation on the Productive and Reproductive Performance of Grazing Primiparous Brahman Cows - R. Soto; I. Rubio; C.S. Galina; E. Castillo; S. Rojas (Tropical Animal Health and Production, 2001)

Effect of abscisic acid and jasmonic acid on partial desiccation of encapsulated somatic embryos of sugarcane - Nadina Nieves; M. E. Martínez; R. Castillo; María A. Blanco; J. L. González-Olmedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Causes and consequences of salt-marsh erosion in an Atlantic estuary in SW Spain - J. M. Castillo; C. J. Luque; E. M. Castellanos; M. E. Figueroa (Journal of Coastal Conservation, 2000)

On the dispersal of riverine colored dissolved organic matter over the West Florida Shelf - Carlos E. Del Castillo; Fernando Gilbes; Paula G. Coble; Frank E. Müller‐Karger (Limnology and Oceanography, 2000)
We investigated the optical properties of surface water in areas of the West Florida Shelf influenced by riverine discharge and by the occurrence of a phytoplankton plume. Results of absorption and fluorescence spectroscopy analyses and determination of dissolved organic carbon (DOC) concentration showed that the injection of riverine colored dissolved organic matter (CDOM) strongly affected the optical properties and DOC concentrations over the shelf. Riverborne nutrients contributed to an increase in primary productivity. However, during the study period, the increase in primary productivity did not result in the production of significant amounts of CDOM. Fluorescence spectroscopy results showed that optical properties of riverine CDOM were lost close to the mouth of the rivers. A simple mathematical model describing mixing between riverine and marine end‐members demonstrated that most of the observed changes in optical properties of CDOM along salinity gradients can be explained by mixing. Laboratory mixing experiments between riverine water and seawater indicated that flocculation of organic matter during estuarine mixing did not affect the optical properties of CDOM. Remote‐sensing studies of the Gulf of Mexico using historical data from the Coastal Zone Color Scanner show a recurrent, seasonal chlorophyll bloom over the West Florida

Mercurialis ambigua and Solanum luteum: Two Newly Discovered Natural Hosts of Tomato Yellow Leaf Curl Geminiviruses - S. Sánchez-Campos; J. Navas-Castillo; F. Monci; J.A. Díaz; E. Moriones (European Journal of Plant Pathology, 2000)

In situ localization of anion exchanger-2 in the human kidney - Jos E. Castillo; Eduardo Martnez-Ans; Raquel Malumbres; Enrique De Alava; Carmen Garca; Juan F. Medina; Jess Prieto (Cell and Tissue Research, 2000)

Investigation of Tuberculosis Contacts in a Nonhospital Pneumology Practice - D. del Castillo Otero; M. Peñafiel Colás; F. Álvarez Gutiérrez; J.G. Soto Campos; E. Calderón Osuna; J. Toral Marín; J. Sánchez Gómez (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Petrology and geochemistry of Camiguin Island, southern Philippines: insights to the source of adakites and other lavas in a complex arc setting - Paterno R. Castillo; Philip E. Janney; Renato U. Solidum (Contributions to Mineralogy and Petrology, 1999)

Synchronous and early activation of planarian Hox genes and the re-specification of body axes during regeneration in Dugesia (G.) tigrina (Turbellaria; Tricladida) - J. R. Bayascas; E. Castillo; A.M. Muñoz-Mármol; J. Baguñà; E. Saló (Hydrobiologia, 1998)

Plasma membrane redox system activity in tumour cell lines of mammary origins with different proliferation rates - A. E. del Valle; A. del Castillo-Olivares; F. Sánchez-Jiménez; J. Márquez; I. Núñez de Castro; M. A. Medina (Protoplasma, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)